Ion exchangeable mixed alkali metal aluminosilicate glasses

By introducing a compressive stress layer and a melt drawing process into alkali metal aluminosilicate glass, the problem of the drop resistance of glass coverings for portable electronic devices has been solved, enabling thinner and higher-strength glass products.

CN120841836APending Publication Date: 2025-10-28CORNING INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510858327.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-11-29
Filing Date
2018-11-29
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

The cover glass of portable electronic devices is susceptible to bending and sharp contact failures when accidentally dropped, and existing technologies struggle to simultaneously improve its durability and mechanical properties to meet the requirements for thinner designs.

Method used

Alkali metal aluminosilicate glass with a specific composition is used to form a compressive stress layer on the glass surface through ion exchange technology, and then combined with a melt drawing process to manufacture thin glass products, thereby improving the strength and toughness of the glass.

Benefits of technology

This technology improves the resistance to bending and sharp contact of glass products without increasing their thickness, meeting the strength and mechanical performance requirements of the cover glass for portable electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120841836A_ABST
    Figure CN120841836A_ABST
Patent Text Reader

Abstract

A glass composition comprising: greater than or equal to 55.0 mol% to less than or equal to 75.0 mol% of SiO2; al2O3 in an amount greater than or equal to 8.0 mol% to less than or equal to 20.0 mol%; li2O in an amount of greater than or equal to 3.0 mol% to less than or equal to 15.0 mol%; greater than or equal to 5.0 mol% to less than or equal to 15.0 mol% of Na2O; and less than or equal to 1.5 mol% of K2O. The glass composition has the following relationships: Al2O3 + Li2O is greater than 22.5 mol%, R2O + RO is greater than or equal to 18.0 mol%, R2O / Al2O3 is greater than or equal to 1.06, SiO2 + Al2O3 + B2O3 + P2O5 is greater than or equal to 78.0 mol%, and (SiO2 + Al2O3 + B2O3 + P2O5) / Li2O is greater than or equal to 8.0. The glass composition may be used in glass articles or consumer electronics.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application filed on November 29, 2018, with application number 201811445318.5 and invention title "Ion-exchangeable mixed alkali metal aluminosilicate glass".

[0002] Related applications

[0003] This application claims priority to U.S. Provisional Application No. 62 / 591,958, filed November 29, 2017, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0004] This specification generally relates to glass compositions suitable for use as cover glass in electronic devices. More specifically, this specification relates to mixed alkali metal aluminosilicate glasses, which can be formed into cover glass for electronic devices by fusion drawing. Background Technology

[0005] The mobile nature of portable devices such as smartphones, tablets, portable media players, personal computers, and cameras makes them particularly vulnerable to accidental drops onto hard surfaces like the ground. These devices often include a cover glass, which can be damaged upon impact with a hard surface. In many of these devices, the cover glass functions as a display screen cover and may also incorporate touch functionality, thus negatively impacting the device's usability when the cover glass is damaged.

[0006] When a portable device is dropped onto a hard surface, there are two main failure modes for the glass cover. One mode is flexure failure, which is caused by the bending of the glass when the device is subjected to dynamic loads from impact with a hard surface. The other mode is sharp contact failure, which is caused by damage introduced into the glass surface. Impact of glass with a rough, hard surface (such as asphalt, granite, etc.) results in sharp indentations in the glass surface. These indentations become failure sites in the glass surface, from which cracks can develop and propagate.

[0007] Ion exchange technology can make glass more resistant to bending failures, including by inducing compressive stress on the glass surface. However, ion-exchanged glass remains susceptible to dynamic sharp contacts due to the high stress concentration caused by localized indentations from sharp contacts.

[0008] Glass manufacturers and handheld device manufacturers have been working to improve the resilience of handheld devices to sharp-contact failures. Solutions range from coatings on the cover glass to the panel itself, preventing the cover glass from directly impacting a hard surface when the device is dropped. However, due to aesthetic and functional limitations, it is difficult to completely prevent the cover glass from impacting hard surfaces.

[0009] It is also desirable for portable devices to be as thin as possible. Therefore, in addition to strength, it is desirable to manufacture the glass used as the cover glass in portable devices to be as thin as possible. Therefore, in addition to increasing the strength of the cover glass, it is desirable for the glass to have the mechanical properties required to be shaped by processes that enable the manufacture of thin glass articles (e.g., thin glass sheets).

[0010] Therefore, there is a demand for glass that can be strengthened, for example, by ion exchange, and that has the mechanical properties required to shape them into thin glass articles. Summary of the Invention

[0011] According to a first embodiment, a glass composition comprises: 55.0 mol% to 75.0 mol% of SiO2; 8.0 mol% to 20.0 mol% of Al2O3; 3.0 mol% to 15.0 mol% of Li2O; 5.0 mol% to 15.0 mol% of Na2O; and 1.5 mol% of K2O, wherein: Al2O3+Li2O is greater than 22.5 mol%, R2O+RO is greater than 18.0 mol%, R2O / Al2O3 is greater than 1.06, SiO2+Al2O3+B2O3+P2O5 is greater than 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than 8.0.

[0012] According to a second embodiment, a glass article includes: a first surface; a second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed by the distance between the first surface and the second surface; and a compressive stress layer extending from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein the central tension of the glass article is greater than or equal to 30 MPa, the compression depth of the compressive stress layer is greater than or equal to 0.15 t and less than or equal to 0.25 t, and the glass article is formed of glass comprising: greater than or equal to 55.0 mol% and less than or equal to 75.0 mol% SiO2; greater than or equal to 8.0 mol% to less than or equal to 20.0 mol% of Al2O3; greater than or equal to 3.0 mol% to less than or equal to 15.0 mol% of Li2O; greater than or equal to 5.0 mol% to less than or equal to 15.0 mol% of Na2O; and less than or equal to 1.5 mol% of K2O, wherein: Al2O3+Li2O is greater than 22.5 mol%, R2O+RO is greater than or equal to 18.0 mol%, R2O / Al2O3 is greater than or equal to 1.06, SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.0.

[0013] According to a third embodiment, a glass article includes: a first surface; a second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed as the distance between the first surface and the second surface; and a compressive stress layer extending from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein the central tension of the glass article is greater than or equal to 60 MPa, the compressive stress layer has a compression depth greater than or equal to 0.15t and less than or equal to 0.25t, and the glass article has a composition at the central depth of the glass article comprising: greater than or equal to 55.0 mol% and less than or equal to 75.0 mol% SiO2. ; ≥8.0 mol% to ≤20.0 mol% Al2O3; ≥3.0 mol% to ≤15.0 mol% Li2O; ≥5.0 mol% to ≤15.0 mol% Na2O; and ≤1.5 mol% K2O, wherein: Al2O3+Li2O is greater than 22.5 mol%, R2O+RO is greater than or equal to 18.0 mol%, R2O / Al2O3 is greater than or equal to 1.06, SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.0.

[0014] Further features and advantages will be set forth in the detailed description below and will be apparent to those skilled in the art to some extent, or will be appreciated by practice of the embodiments described herein (including the detailed description below, the claims and the drawings).

[0015] It should be understood that the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overview or framework for understanding the properties and characteristics of the claimed subject matter. Drawings are included to provide a further understanding of the various embodiments and are incorporated in and form a part of this specification. The drawings illustrate the various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. Attached Figure Description

[0016] Figure 1 A cross-section of a glass having a compressive stress layer on its surface, according to an embodiment disclosed and described herein, is shown schematically.

[0017] Figure 2A It is a plan view of an exemplary electronic device containing any glass article disclosed herein; and

[0018] Figure 2B yes Figure 2A A perspective view of an exemplary electronic device. Detailed Implementation

[0019] Reference will now be made in detail to alkali metal aluminosilicate glasses according to various embodiments. Alkali metal aluminosilicate glasses have good ion exchangeability, and chemical strengthening processes have been used to achieve high strength and high toughness properties in alkali metal aluminosilicate glasses. Sodium aluminosilicate glass is a highly ion-exchangeable glass with high glass formability and quality. Al2O3 substitution into the silicate glass network increases the interdiffusion rate of monovalent cations during ion exchange. By chemical strengthening in a molten salt bath (e.g., KNO3 and / or NaNO3), glasses with high strength, high toughness, and high resistance to indentation cracks can be achieved.

[0020] Therefore, the use of alkali metal aluminosilicate glasses, which possess excellent physical properties, chemical durability, and ion exchangeability, as covering glasses has attracted considerable attention. In particular, this paper presents lithium-containing aluminosilicate glasses with lower annealing and softening temperatures, lower coefficients of thermal expansion (CTE) values, and rapid ion exchangeability. Greater center tension (CT), depth of compression (DOC), and compressive stress (CS) can be achieved through different ion exchange processes. However, the addition of lithium to alkali metal aluminosilicate glasses can lower the glass's melting point, softening point, or liquidus viscosity.

[0021] Drawing processes are desirable for forming glass articles (such as glass sheets) because they allow for the formation of thin glass articles with few defects. It was previously thought that glass compositions needed relatively high liquidus viscosities—e.g., greater than 1000 kP, 1100 kP, or 1200 kP—to be shaped by drawing processes (such as melt drawing or slot drawing). However, advancements in drawing processes have made it possible to use glass with lower liquidus viscosities. Therefore, the glass used in drawing processes can include more lithium oxide than previously thought, and can include more glass network-forming components, such as, for example, SiO2, Al2O3, B2O3, and P2O5. Therefore, this paper provides a balance of various glass components that allows the glass to achieve the benefits of adding lithium and glass network-forming agents to the glass composition without negatively impacting the composition.

[0022] In the embodiments of the glass compositions described herein, unless otherwise stated, the concentrations of the constituent components (e.g., SiO2, Al2O3, Li2O, etc.) are given as mole percentages (mol%) based on oxides. The components of the alkali metal aluminosilicate glass compositions according to each embodiment are discussed below. It should be understood that any of the various ranges of a component can be combined individually with any of the various ranges of any other component.

[0023] In the embodiments of the alkali metal aluminosilicate glass compositions disclosed herein, SiO2 is the most abundant component; for example, SiO2 is the main component of the glass network formed by the glass composition. Pure SiO2 has a relatively low CTE and does not contain alkali metals. However, pure SiO2 has a high melting point. Therefore, if the concentration of SiO2 in the glass composition is too high, the formability of the glass composition may be reduced because a higher concentration of SiO2 increases the difficulty of melting the glass, which in turn adversely affects the formability of the glass. In embodiments, the glass composition typically comprises an amount of SiO2 greater than or equal to 55.0 mol% to less than or equal to 75.0 mol%, and amounts of SiO2 in all ranges and subranges between the aforementioned values. In some embodiments, the glass composition comprises an amount of SiO2 greater than or equal to 58.0 mol%, for example, greater than or equal to 60.0 mol%, greater than or equal to 62.0 mol%, greater than or equal to 64.0 mol%, greater than or equal to 66.0 mol%, greater than or equal to 68.0 mol%, or greater than or equal to 70.0 mol%. In embodiments, the glass composition comprises less than or equal to 72.0 mol% of SiO2, for example, less than or equal to 70.0 mol%, less than or equal to 68.0 mol%, less than or equal to 66.0 mol%, less than or equal to 64.0 mol%, or less than or equal to 62.0 mol%. It should be understood that in various embodiments, any of the foregoing ranges may be combined with any other range. In embodiments, the glass composition comprises more than or equal to 58.0 mol% to less than or equal to 70.0 mol% of SiO2, for example, more than or equal to 60.0 mol% to less than or equal to 68.0 mol%, or more than or equal to 62.0 mol% to less than or equal to 64.0 mol%, and all ranges and subranges between the foregoing values.

[0024] The glass compositions of various embodiments may further include Al2O3. Al2O3 can be used as a glass network forming agent, similar to SiO2. Al2O3 can increase the viscosity of the glass composition due to its tetrahedral coordination in the glass melt formed from the glass composition, and reduces the formability of the glass composition when the amount of Al2O3 is too large. However, when the concentration of Al2O3 is balanced with the concentration of SiO2 and alkali metal oxides in the glass composition, Al2O3 can lower the liquidus temperature of the glass melt, thereby increasing the liquidus viscosity and improving the compatibility of the glass composition with certain forming processes such as melt molding. In embodiments, the glass composition typically includes Al2O3 at a concentration greater than or equal to 8.0 mol% to less than or equal to 20.0 mol%, and concentrations of Al2O3 in all ranges and subranges between the aforementioned values. In some embodiments, the glass composition comprises 10.0 mol% or more of Al2O3, for example, 12.0 mol% or more, 14.0 mol% or more, 16.0 mol% or more, 17.0 mol% or more, or 19.0 mol% or more. In other embodiments, the glass composition comprises less than or equal to 19.0 mol% of Al2O3, for example, 18.0 mol% or more, 17.0 mol% or more, 16.0 mol% or more, 15.0 mol% or more, 14.0 mol% or more, or 13.0 mol% or more. It should be understood that in each embodiment, any of the above ranges may be combined with any other range. In an embodiment, the glass composition comprises an amount of Al2O3 greater than or equal to 10.0 mol% to less than or equal to 18.0 mol%, for example greater than or equal to 12.0 mol% to less than or equal to 16.0 mol%, or greater than or equal to 15.0 mol% to less than or equal to 17.0 mol%, and all ranges and subranges between the foregoing values.

[0025] Similar to SiO2 and Al2O3, P2O5 can be added to glass compositions as a network forming agent, thereby reducing the meltability and formability of the glass composition. Therefore, P2O5 can be added in amounts that do not excessively degrade these properties. The addition of P2O5 can also increase the diffusivity of ions in the glass composition during ion exchange treatment, thereby improving the efficiency of these treatments. In embodiments, the glass composition may include amounts of P2O5 greater than or equal to 0.0 mol% to less than or equal to 8.0 mol%, and amounts within all ranges and subranges between the aforementioned values. In some embodiments, the glass composition may include amounts of P2O5 greater than or equal to 0.5 mol%, greater than or equal to 1.0 mol%, greater than or equal to 1.5 mol%, greater than or equal to 2.0 mol%, greater than or equal to 2.5 mol%, greater than or equal to 3.0 mol%, greater than or equal to 3.5 mol%, greater than or equal to 4.0 mol%, or greater than or equal to 4.5 mol%. In embodiments, the glass composition may include amounts of P2O5 of less than or equal to 7.5 mol%, less than or equal to 7.0 mol%, less than or equal to 6.5 mol%, less than or equal to 6.0 mol%, less than or equal to 5.5 mol%, less than or equal to 5.0 mol%, less than or equal to 4.5 mol%, less than or equal to 4.0 mol%, less than or equal to 3.5 mol%, less than or equal to 3.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.5 mol%, less than or equal to 1.0 mol%, or less than or equal to 0.5 mol%. It should be understood that in various embodiments, any of the above ranges may be combined with any other range. In embodiments, the glass composition may include amounts of P2O5 in quantities greater than or equal to 0.5 mol% to less than or equal to 7.5 mol%, greater than or equal to 1.0 mol% to less than or equal to 7.0 mol%, greater than or equal to 1.5 mol% to less than or equal to 6.5 mol%, greater than or equal to 2.0 mol% to less than or equal to 6.0 mol%, greater than or equal to 2.5 mol% to less than or equal to 5.5 mol%, or greater than or equal to 3.0 mol% to less than or equal to 5.0 mol%, as well as amounts of P2O5 in all ranges and subranges between the aforementioned values.

[0026] Similar to SiO2, Al2O3, and P2O5, B2O3 can be added to glass compositions as a network forming agent, thereby reducing the meltability and formability of the glass composition. Therefore, B2O3 can be added in amounts that do not excessively reduce these properties. In embodiments, the glass composition may include amounts of B2O3 greater than or equal to 0.0 mol% to less than or equal to 3.0 mol%, and amounts in all ranges and subranges between the aforementioned values. In some embodiments, the glass composition may include amounts of B2O3 greater than or equal to 0.5 mol%, greater than or equal to 1.0 mol%, greater than or equal to 1.5 mol%, greater than or equal to 2.0 mol%, or greater than or equal to 2.5 mol%. In embodiments, the glass composition may include amounts of B2O3 less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.5 mol%, less than or equal to 1.0 mol%, or less than or equal to 0.5 mol%. It should be understood that in various embodiments, any of the above ranges may be combined with any other range. In an embodiment, the glass composition comprises an amount of B2O3 greater than or equal to 0.5 mol% to less than or equal to 2.5 mol%, or greater than or equal to 1.0 mol% to less than or equal to 2.0 mol%, as well as amounts of B2O3 in all ranges and subranges between the aforementioned values.

[0027] In some embodiments, the glass composition includes at least one of B2O3 and P2O5 as a glass network forming element. Therefore, in embodiments, B2O3 + P2O5 is greater than 0.0 mol%, for example, greater than or equal to 0.5 mol%, greater than or equal to 1.0 mol%, greater than or equal to 1.5 mol%, greater than or equal to 2.0 mol%, greater than or equal to 2.5 mol%, greater than or equal to 3.0 mol%, greater than or equal to 3.5 mol%, greater than or equal to 4.0 mol%, greater than or equal to 4.5 mol%, greater than or equal to 5.0 mol%, greater than or equal to 5.5 mol%, greater than or equal to 6.0 mol%, greater than or equal to 6.5 mol%, greater than or equal to 7.0 mol%, greater than or equal to 7.5 mol%, or greater than or equal to 8.0 mol%, as well as all ranges and subranges between the foregoing values. In embodiments, B2O3+P2O5 is less than or equal to 7.5 mol%, for example, less than or equal to 7.0 mol%, less than or equal to 6.5 mol%, less than or equal to 6.0 mol%, less than or equal to 5.5 mol%, less than or equal to 5.0 mol%, less than or equal to 4.5 mol%, less than or equal to 4.0 mol%, less than or equal to 3.5 mol%, less than or equal to 3.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.5 mol%, less than or equal to 1.0 mol%, or less than or equal to 0.5 mol%. It should be understood that in various embodiments, any of the above ranges can be combined with any other range. In embodiments, the glass composition comprises amounts of B2O3+P2O5 in quantities greater than or equal to 0.5 mol% to less than or equal to 7.5 mol%, greater than or equal to 1.0 mol% to less than or equal to 7.0 mol%, greater than or equal to 1.5 mol% to less than or equal to 6.5 mol%, greater than or equal to 2.0 mol% to less than or equal to 6.0 mol%, greater than or equal to 2.5 mol% to less than or equal to 5.5 mol%, or greater than or equal to 3.0 mol% to less than or equal to 5.0 mol%, as well as amounts of B2O3+P2O5 in all ranges and subranges between the aforementioned values.

[0028] The role of Li₂O in glass compositions has been discussed above and will be further elaborated below. To some extent, the addition of lithium to glass allows for better control of the ion exchange process and further reduces the softening point of the glass. In embodiments, the glass composition typically comprises an amount of Li₂O greater than or equal to 3.0 mol% to less than or equal to 15.0 mol%, and amounts of Li₂O within all ranges and subranges between the aforementioned values. In some embodiments, the glass composition comprises 3.5 mol% or more, 4.0 mol% or more, 4.5 mol% or more, 5.0 mol% or more, 5.5 mol% or more, 6.0 mol% or more, 6.5 mol% or more, 7.0 mol% or more, 7.5 mol% or more, 8.0 mol% or more, 8.5 mol% or more, 9.0 mol% or more, 9.5 mol% or more, 10.0 mol% or more, 10.5 mol% or more, 11.0 mol% or more, 11.5 mol% or more, 12.0 mol% or more, 12.5 mol% or more, 13.0 mol% or more, 13.5 mol% or more, 14.0 mol% or more, or 14.5 mol% of Li₂O. In some embodiments, the glass composition comprises less than or equal to 14.5 mol%, less than or equal to 14.0 mol%, less than or equal to 13.5 mol%, less than or equal to 13.0 mol%, less than or equal to 12.5 mol%, less than or equal to 12.0 mol%, less than or equal to 11.5 mol%, less than or equal to 11.0 mol%, less than or equal to 10.5 mol%, less than or equal to 10.0 mol%, less than or equal to 9.5 mol%, less than or equal to 9.0 mol%, less than or equal to 8.5 mol%, less than or equal to 8.0 mol%, less than or equal to 7.5 mol%, less than or equal to 7.0 mol%, less than or equal to 6.5 mol%, less than or equal to 6.0 mol%, less than or equal to 5.5 mol%, less than or equal to 5.0 mol%, less than or equal to 4.5 mol%, less than or equal to 4.0 mol%, or less than or equal to 3.5 mol%. It should be understood that in each implementation, any of the above scopes can be combined with any other scope.In embodiments, the glass composition comprises an amount of Li₂O greater than or equal to 3.5 mol% to less than or equal to 14.5 mol%, for example greater than or equal to 4.0 mol% to less than or equal to 14.0 mol%, greater than or equal to 4.5 mol% to less than or equal to 13.5 mol%, greater than or equal to 5.0 mol% to less than or equal to 13.0 mol%, greater than or equal to 5.5 mol% to less than or equal to 12.5 mol%, greater than or equal to 6.0 mol% to less than or equal to 12.0 mol%, greater than or equal to 6.5 mol% to less than or equal to 11.5 mol%, or greater than or equal to 7.0 mol% to less than or equal to 10.0 mol%, as well as all ranges and subranges between the foregoing values.

[0029] In addition to being a glass network-forming component, Al₂O₃ also contributes to improving the ion exchangeability of the glass composition. Therefore, in embodiments, the amounts of Al₂O₃ and other ion-exchangeable components can be relatively high. For example, Li₂O is an ion-exchangeable component. In some embodiments, the amount of Al₂O₃ + Li₂O in the glass composition can be greater than 22.5 mol%, for example, greater than or equal to 23.0 mol%, greater than or equal to 23.5 mol%, greater than or equal to 24.0 mol%, greater than or equal to 24.5 mol%, greater than or equal to 25.0 mol%, greater than or equal to 25.5 mol%, or greater than or equal to 26.0 mol%, as well as all ranges and subranges between the foregoing values. In some embodiments, the amount of Al₂O₃ + Li₂O is less than or equal to 26.5 mol%, for example, less than or equal to 26.0 mol%, less than or equal to 25.5 mol%, less than or equal to 25.0 mol%, less than or equal to 24.5 mol%, less than or equal to 24.0 mol%, less than or equal to 23.5 mol%, or less than or equal to 23.0 mol%, and all ranges and subranges between the foregoing values. It should be understood that in various embodiments, any of the foregoing ranges can be combined with any other range. In embodiments, the amount of Al₂O₃ + Li₂O is greater than or equal to 23.0 mol% to less than or equal to 26.5 mol%, greater than or equal to 3.5 mol% to less than or equal to 26.0 mol%, greater than or equal to 24.0 mol% to less than or equal to 25.5 mol%, or greater than or equal to 24.5 mol% to less than or equal to 25.0 mol%, and all ranges and subranges between the foregoing values.

[0030] According to embodiments, the glass composition may also include an alkali metal oxide other than Li₂O, such as Na₂O. Na₂O contributes to the ion exchangeability of the glass composition and also increases the melting point and improves the formability of the glass composition. However, if too much Na₂O is added to the glass composition, the CTE may be too low and the melting point may be too high. In embodiments, the glass composition typically includes an amount of Na₂O greater than 5.0 mol% to less than or equal to 15 mol%, and amounts of Na₂O within all ranges and subranges between the foregoing values. In some embodiments, the glass composition includes 5.5 mol% or more, 6.0 mol% or more, 6.5 mol% or more, 7.0 mol% or more, 7.5 mol% or more, 8.0 mol% or more, 8.5 mol% or more, 9.0 mol% or more, 9.5 mol% or more, 10.0 mol% or more, 10.5 mol% or more, 11.0 mol% or more, 11.5 mol% or more, 12.0 mol% or more, 12.5 mol% or more, 13.0 mol% or more, 13.5 mol% or more, 14.0 mol% or more, or 14.5 mol% or more. In some embodiments, the glass composition comprises less than or equal to 14.5 mol%, less than or equal to 14.0 mol%, less than or equal to 13.5 mol%, less than or equal to 13.0 mol%, less than or equal to 12.5 mol%, less than or equal to 12.0 mol%, less than or equal to 11.5 mol%, less than or equal to 11.0 mol%, less than or equal to 10.5 mol%, less than or equal to 10.0 mol%, less than or equal to 9.5 mol%, less than or equal to 9.0 mol%, less than or equal to 8.5 mol%, less than or equal to 8.0 mol%, less than or equal to 7.5 mol%, less than or equal to 7.0 mol%, less than or equal to 6.5 mol%, less than or equal to 6.0 mol%, less than or equal to 5.5 mol%, less than or equal to 5.0 mol%, or less than or equal to 4.5 mol% of Na₂O. It should be understood that in each embodiment, any of the above ranges may be combined with any other range.In embodiments, the glass composition comprises an amount of Na₂O greater than or equal to 5.5 mol% to less than or equal to 14.5 mol%, for example greater than or equal to 6.0 mol% to less than or equal to 14.0 mol%, greater than or equal to 6.5 mol% to less than or equal to 13.5 mol%, greater than or equal to 7.0 mol% to less than or equal to 13.0 mol%, greater than or equal to 7.5 mol% to less than or equal to 12.5 mol%, greater than or equal to 8.0 mol% to less than or equal to 12.0 mol%, greater than or equal to 8.5 mol% to less than or equal to 11.5 mol%, or greater than or equal to 9.0 mol% to less than or equal to 10.0 mol%, as well as all ranges and subranges between the foregoing values.

[0031] As described above, Al₂O₃ contributes to improving the ion exchangeability of the glass composition. Therefore, in embodiments, the amounts of Al₂O₃ and other ion-exchangeable components can be relatively high. For example, Li₂O and Na₂O are ion-exchangeable components. In some embodiments, the amount of Al₂O₃ + Li₂O + Na₂O in the glass composition can be greater than 25.0 mol%, for example, greater than or equal to 25.5 mol%, greater than or equal to 26.0 mol%, greater than or equal to 26.5 mol%, greater than or equal to 27.0 mol%, greater than or equal to 27.5 mol%, greater than or equal to 28.0 mol%, greater than or equal to 28.5 mol%, greater than or equal to 29.0 mol%, or greater than or equal to 29.5 mol%, and all ranges and subranges between the foregoing values. In some embodiments, the amount of Al₂O₃ + Li₂O + Na₂O is less than or equal to 30.0 mol%, for example, less than or equal to 29.5 mol%, less than or equal to 29.0 mol%, less than or equal to 28.5 mol%, less than or equal to 28.0 mol%, less than or equal to 27.5 mol%, less than or equal to 27.0 mol%, less than or equal to 26.5 mol%, less than or equal to 26.0 mol%, or less than or equal to 25.5 mol%, as well as all ranges and sub-ranges between the foregoing values. It should be understood that in various embodiments, any of the foregoing ranges can be combined with any other range. In the embodiments, the amount of Al2O3+Li2O+Na2O is greater than or equal to 25.0 mol% to less than or equal to 30.0 mol%, greater than or equal to 25.5 mol% to less than or equal to 29.5 mol%, greater than or equal to 26.0 mol% to less than or equal to 29.0 mol%, greater than or equal to 26.5 mol% to less than or equal to 28.5 mol%, or greater than or equal to 27.0 mol% to less than or equal to 28.0 mol%, as well as all ranges and subranges between the foregoing values.

[0032] Similar to Na₂O, K₂O also promotes ion exchange and increases the DOC of the compressive stress layer. However, adding K₂O can lead to excessively low CTE and excessively high melting point. In embodiments, the glass composition comprises less than or equal to 1.5 mol% K₂O, for example less than or equal to 1.0 mol%, or less than or equal to 0.5 mol%, and all ranges and subranges between the foregoing values. In some embodiments, the glass composition is potassium-free or substantially potassium-free. As used herein, the term "substantially potassium-free" means that the component is not added as a component of the batch, although the component may be present in the final glass as an impurity in very small amounts (e.g., less than 0.01 mol%).

[0033] MgO reduces the viscosity of glass, which improves formability, strain point, and Young's modulus, and can also improve ion exchange capacity. However, when too much MgO is added to the glass composition, the density and CTE of the glass composition increase. In embodiments, the glass composition typically comprises MgO at a concentration of greater than or equal to 0.0 mol% to less than or equal to 4.0 mol%, and at concentrations in all ranges and subranges between the foregoing values. In some embodiments, the glass composition comprises MgO in amounts greater than or equal to 0.2 mol%, greater than or equal to 0.5 mol%, greater than or equal to 1.0 mol%, greater than or equal to 1.5 mol%, greater than or equal to 2.0 mol%, greater than or equal to 2.5 mol%, greater than or equal to 3.0 mol%, or greater than or equal to 3.5 mol%. In some embodiments, the glass composition comprises MgO in amounts less than or equal to 3.5 mol%, less than or equal to 3.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.5 mol%, less than or equal to 1.0 mol%, less than or equal to 0.5 mol%, less than or equal to 0.4 mol%, or less than or equal to 0.2 mol%. It should be understood that in various embodiments, any of the above ranges can be combined with any other range. In embodiments, the glass composition comprises MgO in amounts greater than or equal to 0.2 mol% to less than or equal to 3.5 mol%, for example, greater than or equal to 0.5 mol% to less than or equal to 3.0 mol%, greater than or equal to 1.0 mol% to less than or equal to 2.5 mol%, or greater than or equal to 1.5 mol% to less than or equal to 2.0 mol%, and all ranges and subranges between the foregoing values.

[0034] CaO reduces the viscosity of glass, which improves formability, strain point, and Young's modulus, and can also improve ion exchange capacity. However, when too much CaO is added to the glass composition, the density and CTE of the glass composition increase. In embodiments, the glass composition typically comprises CaO at a concentration greater than or equal to 0.0 mol% to less than or equal to 2.0 mol%, and at concentrations in all ranges and subranges between the aforementioned values. In some embodiments, the glass composition comprises CaO in amounts greater than or equal to 0.2 mol%, greater than or equal to 0.4 mol%, greater than or equal to 0.6 mol%, greater than or equal to 0.8 mol%, greater than or equal to 1.0 mol%, greater than or equal to 1.2 mol%, greater than or equal to 1.4 mol%, greater than or equal to 1.6 mol%, or greater than or equal to 1.8 mol%. In some embodiments, the glass composition comprises an amount of CaO less than or equal to 1.8 mol%, less than or equal to 1.6 mol%, less than or equal to 1.4 mol%, less than or equal to 1.2 mol%, less than or equal to 1.0 mol%, less than or equal to 0.8 mol%, less than or equal to 0.6 mol%, less than or equal to 0.4 mol%, or less than or equal to 0.2 mol%. It should be understood that in various embodiments, any of the above ranges can be combined with any other range. In embodiments, the glass composition comprises an amount of CaO greater than or equal to 0.2 mol% to less than or equal to 1.8 mol%, for example, greater than or equal to 0.4 mol% to less than or equal to 1.6 mol%, greater than or equal to 0.6 mol% to less than or equal to 1.4 mol%, or greater than or equal to 0.8 mol% to less than or equal to 1.2 mol%, and all ranges and subranges between the foregoing values.

[0035] In embodiments, the glass composition may optionally include one or more clarifying agents. In some embodiments, the clarifying agent may include, for example, SnO2. In such embodiments, SnO2 may be present in the glass composition in an amount less than or equal to 0.2 mol%, for example, greater than or equal to 0.0 mol% to less than or equal to 0.1 mol%, and all ranges and subranges between the foregoing values. In embodiments, SnO2 may be present in the glass composition in an amount greater than or equal to 0.0 mol% to less than or equal to 0.2 mol%, or greater than or equal to 0.1 mol% to less than or equal to 0.2 mol%, and all ranges and subranges between the foregoing values. In some embodiments, the glass composition may be SnO2-free or substantially SnO2-free.

[0036] ZnO enhances the ion exchange properties of glass, for example, by increasing the compressive stress of the glass. However, adding too much ZnO may increase density and lead to phase separation. In embodiments, the glass composition may include an amount of ZnO greater than or equal to 0.0 mol% to less than or equal to 2.5 mol%, for example, greater than or equal to 0.2 mol% to less than or equal to 2.0 mol%, or greater than or equal to 0.5 mol% to less than or equal to 1.5 mol%, and all ranges and subranges between the foregoing values. In some embodiments, the glass composition may include an amount of ZnO greater than or equal to 0.3 mol%, greater than or equal to 0.5 mol%, or greater than or equal to 0.8 mol%. In embodiments, the glass composition may include an amount of ZnO less than or equal to 2.0 mol%, for example, less than or equal to 1.5 mol%, or less than or equal to 1.0 mol%. It should be understood that in various embodiments, any of the foregoing ranges may be combined with any other range.

[0037] In addition to the components described above, the glass composition according to the embodiments disclosed herein may include an amount of divalent cationic oxide (referred to herein as RO) greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and amounts of RO in all ranges and subranges between the foregoing values. As used herein, divalent cationic oxide (RO) includes, but is not limited to, MgO, CaO, SrO, BaO, FeO, and ZnO. In some embodiments, the glass composition may include an amount of RO greater than or equal to 0.2 mol%, such as greater than or equal to 0.5 mol%, greater than or equal to 1.0 mol%, greater than or equal to 1.5 mol%, greater than or equal to 2.0 mol%, greater than or equal to 2.5 mol%, greater than or equal to 3.0 mol%, greater than or equal to 3.5 mol%, greater than or equal to 4.0 mol%, or greater than or equal to 4.5 mol%. In embodiments, the glass composition may include an amount of RO less than or equal to 4.5 mol%, such as less than or equal to 4.0 mol%, less than or equal to 3.5 mol%, less than or equal to 3.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.5 mol%, less than or equal to 1.0 mol%, or less than or equal to 0.5 mol%. It should be understood that in each embodiment, any of the above ranges may be combined with any other range. In embodiments, the glass composition may include an amount of RO greater than or equal to 0.2 mol% to less than or equal to 4.5 mol%, such as greater than or equal to 0.5 mol% to less than or equal to 4.0 mol%, greater than or equal to 1.0 mol% to less than or equal to 3.5 mol%, greater than or equal to 1.5 mol% to less than or equal to 3.0 mol%, or greater than or equal to 2.0 mol% to less than or equal to 2.5 mol%, and all ranges and subranges between the foregoing values.

[0038] The amounts of alkali metal oxides (also referred to herein as "R2O") and RO in the glass composition can affect the viscosity of the glass composition; that is, the softening point decreases with increasing R2O+RO content to facilitate the three-dimensional forming process. As used herein, R2O includes Li2O, Na2O, K2O, Rb2O, Cs2O, and Fr2O. In embodiments, the sum of R2O and RO (i.e., R2O+RO) is greater than or equal to 18.0 mol%, for example, greater than or equal to 18.5 mol%, greater than or equal to 19.0 mol%, greater than or equal to 19.5 mol%, greater than or equal to 20.0 mol%, greater than or equal to 20.5 mol%, greater than or equal to 21.0 mol%, greater than or equal to 21.5 mol%, greater than or equal to 22.0 mol%, greater than or equal to 22.5 mol%, or greater than or equal to 23.0 mol%. In embodiments, the sum of R2O and RO is less than or equal to 22.5 mol%, for example, less than or equal to 22.0 mol%, less than or equal to 21.5 mol%, less than or equal to 21.0 mol%, less than or equal to 21.0 mol%, less than or equal to 20.5 mol%, less than or equal to 20.0 mol%, less than or equal to 19.5 mol%, less than or equal to 19.0 mol%, or less than or equal to 18.5 mol%. It should be understood that in various embodiments, any of the above ranges can be combined with any other range. In embodiments, the sum of R2O and RO in the glass composition is greater than or equal to 18.0 mol% and less than or equal to 23.0 mol%, for example, greater than or equal to 18.5 mol% and less than or equal to 22.5 mol%, greater than or equal to 19.0 mol% and less than or equal to 22.0 mol%, greater than or equal to 19.5 mol% and less than or equal to 21.5 mol%, or greater than or equal to 20.0 mol% and less than or equal to 21.0 mol%, as well as all ranges and subranges between the foregoing values.

[0039] In some embodiments, the mol% R2O / Al2O3 ratio is greater than or equal to 1.06. An R2O / Al2O3 ratio greater than 1.06 improves the glass's solubility. Those skilled in the art of glassmaking know that an R2O ratio exceeding Al2O3 significantly improves the solubility of SiO2 in the glass melt. This value is strictly controlled in glass design to increase yield by reducing losses due to inclusions such as silica junctions. In some embodiments, the R2O / Al2O3 molar ratio is greater than or equal to 1.10, for example, greater than or equal to 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, or 2.00. However, if the R2O / Al2O3 ratio is too high, the glass may become more prone to degradation. In embodiments, the molar ratio of R2O / Al2O3 is less than or equal to 2.10, for example, less than or equal to 2.00, less than or equal to 1.90, less than or equal to 1.80, less than or equal to 1.70, less than or equal to 1.60, less than or equal to 1.50, less than or equal to 1.40, less than or equal to 1.30, less than or equal to 1.20, or less than or equal to 1.10. It should be understood that in various embodiments, any of the above ranges can be combined with any other range. In embodiments, the molar ratio of R2O / Al2O3 is greater than or equal to 1.06 and less than or equal to 2.10, for example, greater than or equal to 1.10 and less than or equal to 1.90, greater than or equal to 1.20 and less than or equal to 1.80, or greater than or equal to 1.30 and less than or equal to 1.70, and all ranges and subranges between the aforementioned values.

[0040] In this embodiment, the total amount of the network-forming component (e.g., Al2O3+SiO2+B2O3+P2O5) is greater than or equal to 78.0 mol%, for example, greater than or equal to 78.5 mol%, greater than or equal to 79.0 mol%, greater than or equal to 78.5 mol%, greater than or equal to 80.0 mol%, greater than or equal to 80.5 mol%, greater than or equal to 81.0 mol%, greater than or equal to 81.5 mol%, greater than or equal to 82.0 mol%, greater than or equal to 82.5 mol%, greater than or equal to 83.0 mol%, greater than or equal to 83.5 mol%, or greater than or equal to 84.0 mol%. Having a large amount of network-forming component increases the connectivity and free volume of the glass, making it less brittle and improving its damage resistance. In embodiments, the total amount of the network-forming component is less than or equal to 85.0 mol%, for example, less than or equal to 84.5 mol%, less than or equal to 84.0 mol%, less than or equal to 83.5 mol%, less than or equal to 83.0 mol%, less than or equal to 82.5 mol%, less than or equal to 82.0 mol%, less than or equal to 81.5 mol%, less than or equal to 81.0 mol%, less than or equal to 80.5 mol%, less than or equal to 80.0 mol%, less than or equal to 79.5 mol%, or less than or equal to 79.0 mol%. It should be understood that in various embodiments, any of the above ranges can be combined with any other range. In embodiments, the total amount of the network-forming component is greater than or equal to 78.0 mol% to less than or equal to 85.0 mol%, for example, greater than or equal to 80.0 mol% to less than or equal to 82.0 mol%, or greater than or equal to 80.5 mol% to less than or equal to 81.5 mol%, and all ranges and sub-ranges between the foregoing values.

[0041] In one or more embodiments, the amount of glass network-forming components (e.g., SiO2, Al2O3, B2O3, and P2O5) can be balanced with the amount of Li2O in the glass composition. Without being bound by any particular theory, it is believed that Li2O reduces the free volume in the glass relative to other alkali metal ions, thus reducing resistance to indentation cracking. This is because Li2O has a lower free volume relative to Na+. + Targeting Li +Ion exchange is necessary, therefore the free volume of Li2O should be controlled relative to the increased free volume of the network forming agent (i.e., SiO2, Al2O3, B2O3, and P2O5) to maintain adequate resistance to sharp contact damage. Thus, in some embodiments, the mol% ratio of the glass network forming agent to Li2O (i.e., (SiO2+Al2O3+B2O3+P2O5) / Li2O) is greater than or equal to 8.0, for example, greater than or equal to 8.5, greater than or equal to 9.0, greater than or equal to 9.5, greater than or equal to 10.0, greater than or equal to 10.5, greater than or equal to 11.0, greater than or equal to 11.5, greater than or equal to 12.0, greater than or equal to 12.5, greater than or equal to 13.0, greater than or equal to 13.5, greater than or equal to 14.0, greater than or equal to 14.5, greater than or equal to 15.0, greater than or equal to 15.5, greater than or equal to 16.0, or greater than or equal to 16.5. In other embodiments, (SiO2+Al2O3+B2O3+P2O5) / Li2O is less than or equal to 17.0, for example, less than or equal to 16.5, less than or equal to 16.0, less than or equal to 15.5, less than or equal to 15.0, less than or equal to 14.5, less than or equal to 14.0, less than or equal to 13.5, less than or equal to 13.0, less than or equal to 12.5, less than or equal to 12.0, less than or equal to 11.5, less than or equal to 11.0, less than or equal to 10.5, less than or equal to 10.0, less than or equal to 9.5, less than or equal to 9.0, or less than or equal to 8.5. It should be understood that in each embodiment, any of the above ranges can be combined with any other range. In the implementation, (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.0 and less than or equal to 17.0, for example greater than or equal to 9.0 and less than or equal to 16.0, greater than or equal to 10.0 and less than or equal to 15.0, greater than or equal to 11.0 and less than or equal to 14.0, or greater than or equal to 12.0 and less than or equal to 13.0, as well as all ranges and subranges between the aforementioned values.

[0042] The total amount of Al₂O₃ + Li₂O should be greater than or equal to 23.0 mol%, for example, greater than or equal to 23.5 mol%, greater than or equal to 24.0 mol%, greater than or equal to 24.5 mol%, greater than or equal to 25.0 mol%, greater than or equal to 25.5 mol%, greater than or equal to 26.0 mol%, greater than or equal to 26.5 mol%, greater than or equal to 27.0 mol%, greater than or equal to 27.5 mol%, greater than or equal to 28.0 mol%, greater than or equal to 28.5 mol%, greater than or equal to 29.0 mol%, greater than or equal to 29.5 mol%, or greater than or equal to 30.0 mol%. The total amount of Al₂O₃ + Li₂O should be as high as possible to promote the maximum compressive stress at a given depth for the tail of the ion exchange distribution.

[0043] In one embodiment, the glass article may be substantially free of one or both of arsenic and antimony. In other embodiments, the glass article may be free of one or both of arsenic and antimony.

[0044] The physical properties of the alkali metal aluminosilicate glass compositions disclosed above will now be discussed. These physical properties can be achieved by varying the component content of the alkali metal aluminosilicate glass compositions, as will be discussed in more detail with reference to the examples.

[0045] The glass composition according to the embodiments may have a content greater than or equal to 2.20 g / cm³. 3 Up to 2.60 g / cm³ 3 The density, for example, greater than or equal to 2.25 g / cm³. 3 Up to 2.60 g / cm³ 3 ≥2.30 g / cm 3 Up to 2.60 g / cm³ 3 ≥2.35 g / cm 3 Up to 2.60 g / cm³ 3 ≥2.40 g / cm 3 Up to 2.60 g / cm³ 3 or greater than or equal to 2.45 g / cm³ 3 Up to 2.60 g / cm³ 3 In an embodiment, the glass composition may have a concentration greater than or equal to 2.20 g / cm³. 3 Up to 2.45 g / cm³ 3 The density, for example, greater than or equal to 2.20 g / cm³. 3 Up to 2.40 g / cm³ 3 ≥2.20 g / cm³ 3 Up to 2.35 g / cm³3 ≥2.20 g / cm³ 3 Up to 2.30 g / cm³ 3 or greater than or equal to 2.20 g / cm³ 3 Up to 2.25 g / cm³ 3 , and all ranges and subranges between the aforementioned values. Typically, in alkali metal aluminosilicate glass compositions, with elements such as Na... + or K + Larger, denser alkali metal cations, such as Li, are... + The substitution of smaller alkali metal cations, such as lithium, reduces the density of the glass composition. Therefore, the higher the amount of lithium in the glass composition, the less dense the glass composition will be. The density values ​​described in this disclosure refer to values ​​measured by the buoyancy method according to ASTM C693-93 (2013).

[0046] In embodiments, the liquid phase viscosity of the glass composition is less than or equal to 1000 kP, for example, less than or equal to 800 kP, less than or equal to 600 kP, less than or equal to 400 kP, less than or equal to 200 kP, less than or equal to 100 kP, less than or equal to 75 kP, less than or equal to 60 kP, less than or equal to 50 kP, less than or equal to 40 kP, or less than or equal to 30 kP. In embodiments, the liquid phase viscosity of the glass composition is greater than or equal to 20 kP, for example, greater than or equal to 40 kP, greater than or equal to 60 kP, greater than or equal to 80 kP, greater than or equal to 100 kP, greater than or equal to 120 kP, greater than or equal to 140 kP, or greater than or equal to 160 kP. It should be understood that in each embodiment, any of the above ranges can be combined with any other range. In this embodiment, the liquid phase viscosity of the glass composition is greater than or equal to 20 kP and less than or equal to 1000 kP, for example, greater than or equal to 40 kP and less than or equal to 900 kP, greater than or equal to 60 kP and less than or equal to 800 kP, or greater than or equal to 80 kP and less than or equal to 700 kP, and all ranges and subranges between the foregoing values. The liquid phase viscosity is determined by the following method: First, the liquid phase temperature of the glass is measured according to ASTM C829-81 (2015), entitled "Standard Procedure for Measuring the Liquid Phase Temperature of Glass by Gradient Furnace Method". Next, the viscosity of the glass at the liquid phase temperature is measured according to ASTM C965-96 (2012), entitled "Standard Procedure for Measuring the Viscosity of Glass Above the Softening Point".

[0047] Adding lithium to a glass composition also affects its Young's modulus, shear modulus, and Poisson's ratio. In embodiments, the Young's modulus of the glass composition can be greater than or equal to 65 GPa and less than or equal to 85 GPa, for example, greater than or equal to 67 GPa and less than or equal to 82 GPa, greater than or equal to 70 GPa and less than or equal to 80 GPa, greater than or equal to 72 GPa and less than or equal to 78 GPa, or greater than or equal to 74 GPa and less than or equal to 76 GPa, as well as all ranges and subranges between the foregoing values. In other embodiments, the Young's modulus of the glass composition can be greater than or equal to 66 GPa and less than or equal to 85 GPa, for example, greater than or equal to 68 GPa and less than or equal to 85 GPa, greater than or equal to 70 GPa and less than or equal to 85 GPa, greater than or equal to 72 GPa and less than or equal to 85 GPa, greater than or equal to 74 GPa and less than or equal to 85 GPa, greater than or equal to 76 GPa and less than or equal to 85 GPa, greater than or equal to 78 GPa and less than or equal to 85 GPa, greater than or equal to 80 GPa and less than or equal to 85 GPa, or greater than or equal to 82 GPa and less than or equal to 85 GPa, as well as all ranges and subranges between the foregoing values. In embodiments, the Young's modulus can be greater than or equal to 65 GPa and less than or equal to 84 GPa, for example, greater than or equal to 65 GPa and less than or equal to 82 GPa, greater than or equal to 65 GPa and less than or equal to 80 GPa, greater than or equal to 65 GPa and less than or equal to 78 GPa, greater than or equal to 65 GPa and less than or equal to 76 GPa, greater than or equal to 65 GPa and less than or equal to 74 GPa, greater than or equal to 65 GPa and less than or equal to 72 GPa, greater than or equal to 65 GPa and less than or equal to 70 GPa, greater than or equal to 65 GPa and less than or equal to 68 GPa, or greater than or equal to 65 GPa and less than or equal to 10 GPa, as well as all ranges and subranges between the foregoing values. The Young's modulus values ​​described in this disclosure refer to values ​​measured using the general type of resonant ultrasonic spectroscopy technique described in ASTM E2001-13, entitled "Standard Guide to Resonant Ultrasonic Spectroscopy for Defect Detection in Metallic and Nonmetallic Parts".

[0048] The softening point of the glass composition is affected by the addition of lithium to the glass composition. According to one or more embodiments, the softening point of the glass composition is affected by the addition of lithium to the glass composition. According to one or more embodiments, the softening point of the glass composition can be greater than or equal to 700°C and less than or equal to 930°C, for example, greater than or equal to 705°C and less than or equal to 925°C, greater than or equal to 710°C and less than or equal to 920°C, greater than or equal to 715°C and less than or equal to 915°C, greater than or equal to 720°C and less than or equal to 910°C, greater than or equal to 725°C and less than or equal to 905°C, greater than or equal to 730°C and less than or equal to 900°C, greater than or equal to 735°C and less than or equal to 895°C, greater than or equal to 740°C and less than or equal to 890°C, greater than or equal to 745°C and less than or equal to 885°C, greater than or equal to 750°C and less than or equal to 880°C, greater than or equal to 750°C and less than or equal to 750°C. The softening point is determined using the parallel plate viscosity method according to ASTM C1351M-96 (2012), ranging from 5°C to 875°C, 760°C to 870°C, 765°C to 865°C, 770°C to 860°C, 775°C to 855°C, 780°C to 850°C, 785°C to 845°C, 790°C to 840°C, 795°C to 835°C, 800°C to 830°C, 805°C to 825°C, or 810°C to 820°C, and all ranges and subranges between the aforementioned values.

[0049] Based on the above description, the glass composition according to the embodiments can be formed by any suitable method, such as slot forming, float forming, rolling process, melt forming process, etc.

[0050] A glass article may be characterized by its method of formation. For example, a glass article may be characterized by being float-formable (i.e., formed by the float process), draw-formable, and especially melt-formable or slot-drawable (i.e., formed by a draw process such as melt drawing or slot drawing).

[0051] The glass articles described in some embodiments herein can be formed using a draw process. The draw process produces glass articles with a uniform thickness and a relatively clean surface. Because the average flexural strength of a glass article is controlled by the number and size of surface imperfections, a clean surface with minimal contact has higher initial strength. Furthermore, draw glass articles have a very flat and smooth surface, eliminating the need for expensive grinding and polishing before use in their final applications.

[0052] Some embodiments of the glass article can be described as melt-formable (i.e., formable using a melt-drawing process). The melt-drawing process uses a drawing trough having channels for receiving molten glass material. These channels have weirs that open at the top along the length of the channel on both sides. When the channel is filled with molten material, the molten glass overflows the weirs. Due to gravity, the molten glass flows down the outer surfaces of the drawing trough as two flowing glass films. These outer surfaces of the drawing trough extend downwards and inwards such that they join at the lower edge of the drawing trough. The two flowing glass films join at this edge to fuse and form a single flowing glass article. An advantage of the melt-drawing method is that, because the two glass films flowing through the channel fuse together, the outer surface of the resulting glass article does not contact any part of the equipment. Therefore, the surface properties of the melt-drawn glass article are not affected by this contact.

[0053] Glass articles described in some embodiments herein can be formed using a slit drawing process. The slit drawing process differs from molten drawing. In the slit drawing process, molten raw glass is fed into a drawing trough. The bottom of the drawing trough has a slot with a nozzle that extends the length of the trough. The molten glass flows through the slit / nozzle and is drawn downwards into a continuous glass article and into an annealing zone.

[0054] In one or more embodiments, the glass articles described herein may exhibit an amorphous microstructure and may be substantially free of crystals or microcrystals. In other words, in some embodiments, the glass articles do not include glass-ceramic materials.

[0055] As described above, in the embodiments, the alkali metal aluminosilicate glass composition can be strengthened, for example, through ion exchange, so that the glass has damage resistance for applications such as, but not limited to, glass for display screen covers. Reference Figure 1 The glass has a first region under compressive stress (e.g., Figure 1 The first compression layer 120 and the second compression layer 122 extend from the surface to the compression depth (DOC) of the glass; and the second region (e.g., Figure 1The central region (130) extends from the DOC to the center or interior region of the glass under tensile stress or central tension (CT). As used herein, DOC refers to the depth at which the stress in a glass article changes from compression to tension. At the DOC, the stress transitions from positive (compressive) stress to negative (tensile) stress, thus exhibiting a stress value of 0.

[0056] According to conventions commonly used in the art, compressive or tensile stress is expressed as negative (<0) stress, and tensile or tensile stress is expressed as positive (>0) stress. However, throughout this specification, CS is expressed as a positive or absolute value, i.e., as stated herein, CS = |CS|. Compressive stress (CS) has a maximum value at or near the glass surface, and CS varies as a function of distance d from the surface. See again Figure 1 The first segment 120 extends from the first surface 110 to a depth d1, and the second segment 122 extends from the second surface 112 to a depth d2. These segments together define the compressive stress, or CS, of the glass 100. The compressive stress (including the surface CS) is measured using a surface stress meter (FSM) with a commercially available instrument, such as the FSM-6000 manufactured by Orihara Industries, Ltd. (Japan). The surface stress measurement depends on the accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. The SOC is measured sequentially according to Procedure C (glass disk method) as described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Stress-Optical Coefficient of Glass," the contents of which are incorporated herein by reference in their entirety.

[0057] In some implementations, CS is greater than or equal to 450 MPa and less than or equal to 800 MPa, for example, greater than or equal to 475 MPa and less than or equal to 775 MPa, greater than or equal to 500 MPa and less than or equal to 750 MPa, greater than or equal to 525 MPa and less than or equal to 725 MPa, greater than or equal to 550 MPa and less than or equal to 700 MPa, greater than or equal to 575 MPa and less than or equal to 675 MPa, or greater than or equal to 600 MPa and less than or equal to 650 MPa, as well as all ranges and subranges between the aforementioned values.

[0058] In one or more embodiments, Na + and K + Ions are exchanged into the glass, and Na + Ion ratio K + Ions diffuse deeper into the glass. K +The depth of ion penetration (“potassium DOL”) differs from DOC because it represents the depth of potassium penetration during ion exchange. For the articles described herein, potassium DOL is typically less than DOC. Potassium DOL is measured using a surface stress meter, such as the commercially available FSM-6000 surface stress meter manufactured by Orihara Industries, Ltd. (Japan), depending on the accurate measurement of the stress optical coefficient (SOC), as described above in the reference CS measurement. The potassium DOL for each of the first compression layer 120 and the second compression layer 122 is greater than or equal to 5 μm and less than or equal to 45 μm, for example, greater than or equal to 6 μm and less than or equal to 40 μm, greater than or equal to 7 μm and less than or equal to 35 μm, greater than or equal to 8 μm and less than or equal to 30 μm, or greater than or equal to 9 μm and less than or equal to 25 μm, as well as all ranges and subranges between the aforementioned values. In one embodiment, the potassium DOL of each of the first compression layer 120 and the second compression layer 122 is greater than or equal to 6 μm and less than or equal to 45 μm, greater than or equal to 10 μm and less than or equal to 45 μm, greater than or equal to 15 μm and less than or equal to 45 μm, greater than or equal to 20 μm and less than or equal to 45 μm, or greater than or equal to 25 μm and less than or equal to 45 μm, and all ranges and subranges between the aforementioned values. In another embodiment, the potassium DOL of each of the first compression layer 120 and the second compression layer 122 is greater than or equal to 5 μm and less than or equal to 35 μm, greater than or equal to 5 μm and less than or equal to 30 μm, greater than or equal to 5 μm and less than or equal to 25 μm, or greater than or equal to 5 μm and less than or equal to 15 μm, and all ranges and subranges between the aforementioned values.

[0059] Two main surfaces ( Figure 1The compressive stresses at 110 and 112 in the glass are balanced by the tension stored in the central region (130) of the glass. The maximum central tension (CT) and DOC value are measured using a scattered light polarizer (SCALP) technique known in the art. The refractive near-field (RNF) method or SCALP can be used to measure the stress distribution. When measuring the stress distribution using the RNF method, the maximum CT value provided by SCALP is used for the RNF method. Specifically, the stress distribution measured by the RNF is force-balanced and calibrated to the maximum CT value provided by the SCALP measurement. The RNF method is described in U.S. Patent No. 8,854,623, entitled “System and Method for Measuring Distribution Characteristics of Glass Samples,” the entire contents of which are incorporated herein by reference. Specifically, the RNF method involves placing the glass article near a reference block, generating a polarization-switched beam that switches between orthogonal polarizations at a rate between 1 Hz and 50 Hz, measuring the power quantity in the polarization-switched beam, and generating a polarization-switched reference signal, wherein the power quantity measured in each orthogonal polarization is within 50% of each other. The method further includes transmitting a polarization-switched beam through a glass sample and a reference block at different depths into the glass sample, then using a relay optics system to relay the transmitted polarization-switched beam to a signal photodetector, and using the signal photodetector to generate a polarization-switched detector signal. The method also includes dividing the detector signal by the reference signal to form a normalized detector signal, and determining the distribution characteristics of the glass sample from the normalized detector signal.

[0060] In embodiments, the glass composition may have a maximum CT greater than or equal to 30 MPa, for example, greater than or equal to 35 MPa, greater than or equal to 40 MPa, greater than or equal to 45 MPa, greater than or equal to 50 MPa, greater than or equal to 55 MPa, greater than or equal to 60 MPa, greater than or equal to 65 MPa, greater than or equal to 70 MPa, greater than or equal to 75 MPa, greater than or equal to 80 MPa, or greater than or equal to 85 MPa, as well as all ranges and subranges between the foregoing values. In embodiments, the glass composition may have a maximum CT less than or equal to 100 MPa, for example, less than or equal to 95 MPa, less than or equal to 90 MPa, less than or equal to 85 MPa, less than or equal to 80 MPa, less than or equal to 75 MPa, less than or equal to 70 MPa, less than or equal to 65 MPa, less than or equal to 60 MPa, less than or equal to 55 MPa, less than or equal to 50 MPa, less than or equal to 45 MPa, or less than or equal to 40 MPa. It should be understood that, in each embodiment, any of the above ranges can be combined with any other range. In embodiments, the glass composition may have a maximum CT greater than or equal to 30 MPa and less than or equal to 100 MPa, for example, greater than or equal to 35 MPa and less than or equal to 95 MPa, greater than or equal to 40 MPa and less than or equal to 90 MPa, greater than or equal to 45 MPa and less than or equal to 85 MPa, greater than or equal to 50 MPa and less than or equal to 80 MPa, greater than or equal to 55 MPa and less than or equal to 75 MPa, or greater than or equal to 60 MPa and less than or equal to 70 MPa, as well as all ranges and subranges between the foregoing values.

[0061] As described above, the Depth of Compression (DOC) is measured using a Scattered Light Polarizing Mirror (SCALP) technique known in the art. In some embodiments herein, the DOC is provided as a portion of the thickness (t) of the glass article. In embodiments, the glass composition may have a Depth of Compression (DOC) greater than or equal to 0.15t and less than or equal to 0.25t, for example, greater than or equal to 0.18t and less than or equal to 0.22t, or greater than or equal to 0.19t and less than or equal to 0.21t, and all ranges and subranges between the foregoing values. In embodiments, the glass composition may have a DOC greater than or equal to 0.16t and less than or equal to 0.20t, for example greater than or equal to 0.17t and less than or equal to 0.25t, greater than or equal to 0.18t and less than or equal to 0.25t, greater than or equal to 0.19t and less than or equal to 0.25t, greater than or equal to 0.20t and less than or equal to 0.25t, greater than or equal to 0.21t and less than or equal to 0.25t, greater than or equal to 0.22t and less than or equal to 0.25t, greater than or equal to 0.23t and less than or equal to 0.25t, or greater than or equal to 0.24t and less than or equal to 0.25t, as well as all ranges and subranges between the aforementioned values. In embodiments, the glass composition may have a DOC greater than or equal to 0.15t and less than or equal to 0.24t, for example greater than or equal to 0.15t and less than or equal to 0.23t, greater than or equal to 0.15t and less than or equal to 0.22t, greater than or equal to 0.15t and less than or equal to 0.21t, greater than or equal to 0.15t and less than or equal to 0.20t, greater than or equal to 0.15t and less than or equal to 0.19t, greater than or equal to 0.15t and less than or equal to 0.18t, greater than or equal to 0.15t and less than or equal to 0.17t, or greater than or equal to 0.15t and less than or equal to 0.16t, as well as all ranges and subranges between the aforementioned values.

[0062] By exposing glass to an ion-exchange solution, a compressive stress layer can be formed in the glass. In some embodiments, the ion-exchange solution may be molten nitrate. In some embodiments, the ion-exchange solution may be molten KNO3, molten NaNO3, or a combination thereof. In some embodiments, the ion-exchange solution may include about 80% molten KNO3, about 75% molten KNO3, about 70% molten KNO3, about 65% molten KNO3, or about 60% molten KNO3. In some embodiments, the ion-exchange solution may include about 20% molten NaNO3, about 25% molten NaNO3, about 30% molten NaNO3, about 35% molten NaNO3, or about 40% molten NaNO3. In embodiments, the ion exchange solution may comprise about 80% molten KNO3 and about 20% molten NaNO3, about 75% molten KNO3 and about 25% molten NaNO3, about 70% molten KNO3 and about 30% molten NaNO3, about 65% molten KNO3 and about 35% molten NaNO3, or about 60% molten KNO3 and about 40%, and all ranges and subranges between the foregoing values. In embodiments, other sodium and potassium salts may be used in the ion exchange solution, such as, for example, sodium nitrite or potassium nitrite, phosphates, or sulfates. In some embodiments, the ion exchange solution may include lithium salts, such as LiNO3.

[0063] Glass compositions can be exposed to ion exchange solutions by immersing glass articles made of the glass composition in an ion exchange solution bath, spraying the ion exchange solution onto the glass articles made of the glass composition, or otherwise physically applying the ion exchange solution to the glass articles made of the glass composition. When exposed to the glass composition, according to embodiments, the ion exchange solution can be at a temperature greater than or equal to 400°C and less than or equal to 500°C, for example, greater than or equal to 410°C and less than or equal to 490°C, greater than or equal to 420°C and less than or equal to 480°C, greater than or equal to 430°C and less than or equal to 470°C, or greater than or equal to 440°C and less than or equal to 460°C, and all ranges and subranges between the aforementioned values. In embodiments, the glass composition may be exposed to an ion-exchange solution for a duration of greater than or equal to 4 hours and less than or equal to 48 hours, for example, greater than or equal to 8 hours and less than or equal to 44 hours, greater than or equal to 12 hours and less than or equal to 40 hours, greater than or equal to 16 hours and less than or equal to 36 hours, greater than or equal to 20 hours and less than or equal to 32 hours, or greater than or equal to 24 hours and less than or equal to 28 hours, as well as all ranges and subranges between the aforementioned values.

[0064] Ion exchange processes can be carried out in ion exchange solutions under treatment conditions that provide improved compressive stress distribution, for example, as disclosed in U.S. Patent Application Publication No. 2016 / 0102011, which is incorporated herein by reference in its entirety.

[0065] After the ion exchange process, it should be understood that the composition at the surface of the glass article can differ from that of the virgin (as-formed) glass article (i.e., the glass article before undergoing the ion exchange process). This is because, in the virgin glass, there are components such as, for example, Li... + Or Na + An alkali metal ion is respectively reacted with, for example, Na + or K + The glass composition is replaced by larger alkali metal ions. However, in embodiments, the glass composition at or near the center of the depth of the glass article will still have the composition of the original (non-ion-exchanged) glass used to form the glass article.

[0066] The glass articles disclosed herein may be incorporated into another article, such as articles having a display (or display articles) (e.g., consumer electronics, including mobile phones, tablets, computers, navigation systems, etc.), building articles, transportation articles (e.g., automobiles, trains, airplanes, marine vessels, etc.), appliance articles, or any article requiring a certain degree of transparency, scratch resistance, abrasion resistance, or a combination thereof. Exemplary articles containing any glass articles disclosed herein are shown in [illustration / example]. Figure 2A and Figure 2B In China. Specifically, Figure 2A and 2B A consumer electronic device 200 is shown, comprising: a housing 202 having a front surface 204, a rear surface 206, and side surfaces 208; electrical components (not shown) at least partially or completely located within the housing, and including at least a controller, memory, and a display 210 located at or near the front surface of the housing; and a cover substrate 212 located on or above the front surface of the housing such that it is positioned above the display. In some embodiments, a portion of the cover substrate 212 and / or a portion of the housing 202 may include any glasswork disclosed herein.

[0067] The first claim includes a glass composition comprising: 55.0 mol% to 75.0 mol% of SiO2; 8.0 mol% to 20.0 mol% of Al2O3; 3.0 mol% to 15.0 mol% of Li2O; 5.0 mol% to 15.0 mol% of Na2O; and 1.5 mol% of K2O, wherein: Al2O3+Li2O is greater than 22.5 mol%, R2O+RO is greater than 18.0 mol%, R2O / Al2O3 is greater than 1.06, SiO2+Al2O3+B2O3+P2O5 is greater than 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than 8.0.

[0068] The second item includes the glass composition according to the first item, wherein Al2O3 + Li2O is greater than or equal to 23.0 mol%.

[0069] The third item comprises a glass composition according to any one of the first and second items, wherein Al2O3 + Li2O is greater than or equal to 23.0 mol% to less than or equal to 26.5 mol%.

[0070] The fourth item comprises a glass composition according to any one of the first to third items, wherein the R2O+RO content is greater than or equal to 18.0 mol% to less than or equal to 23.0 mol%.

[0071] The fifth item comprises a glass composition according to any one of the first to fourth items, wherein the R2O+RO content is greater than or equal to 19.0 mol% to less than or equal to 22.0 mol%.

[0072] The sixth item comprises a glass composition according to any one of the first to fifth items, wherein the R2O / Al2O3 ratio is greater than or equal to 1.06 and less than or equal to 2.10.

[0073] The seventh item comprises a glass composition according to any one of the first to sixth items, wherein the R2O / Al2O3 ratio is greater than or equal to 1.10 and less than or equal to 1.90.

[0074] The eighth item comprises a glass composition according to any one of the first to seventh items, wherein SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol% to less than or equal to 85.0 mol%.

[0075] The ninth item comprises a glass composition according to any one of the first to eighth items, wherein SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol% to less than or equal to 83.0 mol%.

[0076] The tenth item comprises a glass composition according to any one of the first to ninth items, wherein (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.0 and less than or equal to 17.0.

[0077] The eleventh item comprises a glass composition according to any one of the first to tenth items, wherein (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 10.0 and less than or equal to 15.0.

[0078] The twelfth item comprises a glass composition according to any one of the first to eleventh items, wherein the B2O3+P2O5 is greater than 0.0 mol%.

[0079] The thirteenth item includes a glass article comprising: a first surface; a second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed as the distance between the first surface and the second surface; and a compressive stress layer extending from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein the central tension of the glass article is greater than or equal to 30 MPa, the compressive stress layer has a compression depth greater than or equal to 0.15 t and less than or equal to 0.25 t, and the glass article is formed of glass comprising: greater than or equal to 55.0 mol% and less than or equal to 75.0 mol% SiO2; greater than or equal to 8 0 mol% to less than or equal to 20.0 mol% of Al2O3; greater than or equal to 3.0 mol% to less than or equal to 15.0 mol% of Li2O; greater than or equal to 5.0 mol% to less than or equal to 15.0 mol% of Na2O; and less than or equal to 1.5 mol% of K2O, wherein: Al2O3+Li2O is greater than 22.5 mol%, R2O+RO is greater than or equal to 18.0 mol%, R2O / Al2O3 is greater than or equal to 1.06, SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.0.

[0080] The fourteenth item includes the glass article according to the thirteenth item, wherein the center tension of the glass article is greater than or equal to 50 MPa.

[0081] The fifteenth item includes a glass article according to any one of the thirteenth and fourteenth items, wherein the center tension of the glass article is greater than or equal to 80 MPa.

[0082] The sixteenth item includes a glass article according to any one of items thirteen to fifteen, wherein the potassium in the compressive stress layer penetrates the thickness of the glass article to a depth greater than 5 μm and less than or equal to 45 μm.

[0083] The seventeenth item includes a glass article according to any one of the thirteenth to sixteenth items, wherein the liquid phase viscosity of the glass is greater than or equal to 20 kP and less than 1000 kP.

[0084] The eighteenth item includes a glass article according to any one of the thirteenth to seventeenth items, wherein the surface compressive stress of the compressive stress layer is greater than or equal to 450 MPa and less than or equal to 800 MPa.

[0085] The nineteenth item includes a consumer electronic product comprising: a housing including a front surface, a rear surface and a side surface; electrical components located at least partially within the housing, the electrical components including at least a controller, a memory and a display, the display being located at or near the front surface of the housing; and a cover substrate disposed above the display, wherein at least a portion of at least one of the housing and the cover substrate comprises glass article according to any one of the thirteenth to eighteenth items.

[0086] The twentieth claim includes a glass article comprising: a first surface; a second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed as a distance between the first surface and the second surface; and a compressive stress layer extending from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein the central tension of the glass article is greater than or equal to 60 MPa, the compressive stress layer has a compression depth greater than or equal to 0.15 t and less than or equal to 0.25 t, and the glass article has a composition at the central depth of the glass article comprising: greater than or equal to 55.0 mol% and less than or equal to 75.0 mol% of SiO2; The following are the contents of Al2O3, which are greater than or equal to 8.0 mol% and less than or equal to 20.0 mol%; Li2O, which are greater than or equal to 3.0 mol% and less than or equal to 15.0 mol%; Na2O, which are greater than or equal to 5.0 mol% and less than or equal to 15.0 mol%; and K2O, which are less than or equal to 1.5 mol%, wherein Al2O3+Li2O is greater than 22.5 mol%, R2O+RO is greater than or equal to 18.0 mol%, R2O / Al2O3 is greater than or equal to 1.06, SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.0.

[0087] The twenty-first claim includes a glass composition comprising: 55.0 mol% to 70.0 mol% of SiO2; 10.0 mol% to 20.0 mol% of Al2O3; 3.0 mol% to 15.0 mol% of Li2O; 5.0 mol% to 15.0 mol% of Na2O; and 1.5 mol% of K2O, wherein Al2O3+Li2O is greater than 22.5 mol%, R2O+RO is greater than 18.0 mol%, SiO2+Al2O3+B2O3+P2O5 is greater than 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than 10.50.

[0088] The twenty-second claim includes a glass article comprising: a first surface; a second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed as the distance between the first surface and the second surface; and a compressive stress layer extending from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein the central tension of the glass article is greater than or equal to 30 MPa, the compressive stress layer has a compression depth greater than or equal to 0.15 t and less than or equal to 0.25 t, and the glass article is formed of glass according to the twenty-first claim.

[0089] The 23rd item includes the glass article according to the 22nd item, wherein the center tension of the glass article is greater than or equal to 50 MPa.

[0090] The twenty-fourth item includes a glass article according to any one of the twenty-two and twenty-three items, wherein the center tension of the glass article is greater than or equal to 80 MPa.

[0091] The 25th item includes a glass article according to any one of the 22nd to 24th items, wherein the potassium in the compressive stress layer penetrates the thickness of the glass article to a depth greater than 5 μm and less than or equal to 45 μm.

[0092] The twenty-sixth item includes a glass article according to any one of the twenty-two to twenty-five items, wherein the liquid phase viscosity of the glass is greater than or equal to 20 kP and less than 1000 kP.

[0093] The twenty-seventh item includes a glass article according to any one of the twenty-two to twenty-sixth items, wherein the surface compressive stress of the compressive stress layer is greater than or equal to 450 MPa and less than or equal to 800 MPa.

[0094] The twenty-eighth item includes a consumer electronic product comprising: a housing including a front surface, a rear surface and a side surface; electrical components located at least partially within the housing, the electrical components including at least a controller, a memory and a display, the display being located at or near the front surface of the housing; and a cover substrate disposed above the display, wherein at least a portion of at least one of the housing and the cover substrate comprises glass article according to any one of the twenty-two to twenty-seven items.

[0095] Example

[0096] The following examples further illustrate the implementation methods. It should be understood that these examples are not limited to the implementation methods described above.

[0097] Glass compositions having the components listed in Table 1 below were prepared by conventional glass-forming methods. In Table 1, all components are expressed in mol%, and various properties of the glass compositions were measured according to the methods disclosed in this specification.

[0098] Table 1

[0099] sample 1 2 3 4 5 6 7 8 9 10 <![CDATA[SiO2]]> 64.35 63.38 62.28 61.30 60.28 59.35 64.52 63.36 62.47 61.40 <![CDATA[Al2O3]]> 16.33 16.26 16.30 16.32 16.36 16.34 16.16 16.32 16.21 16.30 <![CDATA[P2O5]]> 0.00 0.96 1.94 2.93 3.91 4.86 0.00 0.98 1.91 2.93 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 7.19 7.27 7.35 7.39 7.39 7.39 7.53 7.71 7.79 7.83 <![CDATA[Na2O]]> 12.05 12.05 12.05 11.99 11.97 11.99 11.70 11.53 11.54 11.46 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 ZnO 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 23.52 23.53 23.65 23.71 23.75 23.72 23.69 24.04 24.00 24.13 <![CDATA[R2O]]> 19.25 19.33 19.41 19.39 19.37 19.39 19.25 19.26 19.34 19.30 <![CDATA[R2O+RO]]> 19.27 19.35 19.43 19.40 19.40 19.41 19.27 19.28 19.36 19.32 <![CDATA[Li2O / Na2O]]> 0.60 0.60 0.61 0.62 0.62 0.62 0.64 0.67 0.67 0.68 <![CDATA[SiO2+Al2O3]]> 80.68 79.64 78.58 77.62 76.64 75.68 80.68 79.69 78.68 77.70 <![CDATA[R2O / Al2O3]]> 1.18 1.19 1.19 1.19 1.18 1.19 1.19 1.18 1.19 1.18 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.68 80.60 80.52 80.55 80.55 80.54 80.68 80.67 80.59 80.63 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 11.22 11.09 10.96 10.90 10.90 10.90 10.71 10.46 10.35 10.29 <![CDATA[Density (g / cm 3 )]]> 2.438 2.433 2.428 2.423 2.419 2.414 2.439 2.432 2.427 2.423 Strain point (°C) 542 555 564 565 561 548 538 555 564 566 Annealing point (°C) 591 605 614 615 611 598 586 605 615 616 Softening point (°C) 836.2 848.6 854.7 858.6 854 849.3 826.2 845.1 854.7 854.2 <![CDATA[10 11 Poise temperature (°C) 674 689 697 699 694 683 667 688 699 699 <![CDATA[CTE*10 -7 (1 / ℃)]]> 84.8 85.7 86.5 86 86.5 86.2 84.3 85 84.6 85 Fulchers A -3.789 -3.451 -3.171 -3.43 -2.873 -3.055 -3.478 -3.497 -3.161 -3.083 Fulchers B 10641.6 9417.5 8603.9 9096 7750.1 8143.9 9775.3 9535.6 8556.3 8276.4 Fulchers To -124.5 -21.8 44.9 18.3 107.4 78.2 -75.3 -28 45.1 71.1 200P temperature (°C) 1623 1615 1617 1605 1605 1599 1616 1617 1612 1608 35000P temperature (°C) 1153 1156 1160 1159 1152 1150 1143 1158 1156 1156 200000P temperature (°C) 1046 1054 1060 1060 1056 1053 1038 1056 1056 1058 Liquid phase viscosity (kiloPoise) 575 526 957 1067 1020 2190 452 328 458 540 SOC (nm / mm / MPa) 2.88 2.908 2.92 2.917 2.959 2.927 2.882 2.883 2.91 2.911 Refractive index 1.5114 1.5094 1.5073 1.5055 1.5036 1.5029 1.5119 1.5098 1.5077 1.506 Young's modulus (GPa) 79.6 78.2 77.4 76.1 74.6 73.7 80.2 78.9 77.3 76.3

[0100] Table 1 - Continuation

[0101] sample 11 12 13 14 15 16 17 18 19 20 <![CDATA[SiO2]]> 60.29 59.46 64.31 63.32 62.48 61.36 60.29 59.43 59.89 60.39 <![CDATA[Al2O3]]> 16.31 16.25 16.19 16.30 16.19 16.33 16.36 16.32 16.31 16.26 <![CDATA[P2O5]]> 3.93 4.84 0.00 0.97 1.99 2.92 3.97 4.91 4.91 4.90 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 7.92 7.95 8.12 8.21 8.21 8.31 8.33 8.33 8.35 8.42 <![CDATA[Na2O]]> 11.48 11.42 11.30 11.12 11.05 11.00 10.97 10.94 10.46 9.95 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 ZnO 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 24.22 24.20 24.31 24.51 24.40 24.64 24.69 24.65 24.65 24.69 <![CDATA[R2O]]> 19.40 19.37 19.42 19.34 19.26 19.31 19.31 19.28 18.82 18.38 <![CDATA[R2O+RO]]> 19.42 19.39 19.44 19.36 19.28 19.33 19.33 19.30 18.84 18.40 <![CDATA[Li2O / Na2O]]> 0.69 0.70 0.72 0.74 0.74 0.76 0.76 0.76 0.80 0.85 <![CDATA[SiO2+Al2O3]]> 76.60 75.71 80.51 79.62 78.68 77.69 76.65 75.75 76.20 76.66 <![CDATA[R2O / Al2O3]]> 1.19 1.19 1.20 1.19 1.19 1.18 1.18 1.18 1.15 1.13 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.53 80.56 80.51 80.59 80.67 80.62 80.62 80.65 81.11 81.55 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 10.17 10.13 9.92 9.81 9.83 9.70 9.68 9.68 9.72 9.68 <![CDATA[Density (g / cm 3 )]]> 2.418 2.414 2.437 2.429 2.425 2.42 2.417 2.413 2.409 2.404 Strain point (°C) 561 555 531 554 560 565 561 552 553 557 Annealing point (°C) 610 605 579 602 610 614 611 602 602 607 Softening point (°C) 851.5 849.5 815.1 842.5 846.5 855 850.6 843.3 847 853 <![CDATA[10 11 Poise temperature (°C) 692 689 660 683 692 696 694 685 685 691 <![CDATA[CTE*10 -7 (1 / ℃)]]> 86 85.8 84.3 84.1 84.2 84.9 85.4 85.1 82.7 81.4 Fulchers A -3.564 -3.164 -3.476 -3.824 -3.254 -2.999 -3.349 -3.189 -2.854 -3.191 Fulchers B 9520.9 8372.3 9779.2 10717.7 8803.7 8062.7 8831 8366.6 7673 8433.7 Fulchers To -45.9 58 -93.3 -150.9 7.6 83.2 27.2 57.3 105.4 67.4 200P temperature (°C) 1577 1590 1599 1599 1592 1604 1590 1581 1594 1603 35000P temperature (°C) 1128 1144 1126 1130 1137 1152 1146 1139 1143 1158 200000P temperature (°C) 1028 1047 1021 1024 1037 1055 1048 1043 1046 1061 Liquid phase viscosity (kiloPoise) 424 1312 223 179 206 405 536 756 474 512 SOC (nm / mm / MPa) 2.906 2.919 2.865 2.892 2.912 2.922 2.931 2.941 2.935 2.966 Refractive index 1.5041 1.5026 1.5126 1.5101 1.5081 1.5063 1.5048 1.5033 1.5028 1.5021 Young's modulus (GPa) 75.1 74.1 80.4 79.2 78.1 76.7 75.8 74.6 74.0 74.6

[0102] Table 1 - Continuation

[0103] sample 21 22 23 24 25 26 27 28 29 30 <![CDATA[SiO2]]> 59.90 60.19 59.84 60.10 61.40 61.36 61.32 61.37 61.39 61.45 <![CDATA[Al2O3]]> 16.31 16.38 16.40 16.45 16.25 16.30 16.33 16.29 16.25 16.29 <![CDATA[P2O5]]> 4.91 4.94 4.95 4.99 2.91 2.92 2.91 2.92 2.92 2.89 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 8.84 8.95 9.24 9.37 8.38 8.41 8.37 8.34 8.39 8.38 <![CDATA[Na2O]]> 9.95 9.46 9.49 9.00 9.99 9.99 10.07 9.02 9.05 9.00 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 0.02 0.02 0.02 0.02 1.01 0.02 0.49 2.00 0.02 1.00 ZnO 0.00 0.00 0.00 0.00 0.00 0.94 0.46 0.00 1.92 0.93 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 25.15 25.34 25.63 25.82 24.63 24.71 24.69 24.64 24.64 24.66 <![CDATA[R2O]]> 18.80 18.42 18.73 18.38 18.38 18.41 18.44 17.37 17.45 17.39 <![CDATA[R2O+RO]]> 18.82 18.44 18.75 18.40 19.39 19.36 19.39 19.37 19.39 19.32 <![CDATA[Li2O / Na2O]]> 0.89 0.95 0.97 1.04 0.84 0.84 0.83 0.93 0.93 0.93 <![CDATA[SiO2+Al2O3]]> 76.21 76.57 76.24 76.55 77.65 77.67 77.65 77.66 77.64 77.74 <![CDATA[R2O / Al2O3]]> 1.15 1.12 1.14 1.12 1.13 1.13 1.13 1.07 1.07 1.07 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 81.13 8151 81.19 81.55 80.56 80.59 80.56 80.58 80.56 80.63 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 9.18 9.11 8.79 8.70 9.61 9.58 9.63 9.66 8.60 9.63 <![CDATA[Density (g / cm 3 )]]> 2.407 2.403 2.406 2.401 2.421 2.435 2.425 2.422 2.448 2.436 Strain point (°C) 557 558 554 560 566 562 565 573 561 565 Annealing point (°C) 606 608 604 609 615 611 614 621 611 614 Softening point (°C) 843 852 843 853 856.4 854 854.8 861.8 853.9 855.8 <![CDATA[10 11 Poise temperature (°C) 688 692 687 692 697 693 696 702 694 696 <![CDATA[CTE*10 -7 (1 / ℃)]]> 82.9 80.5 81.9 79.8 81 80.1 80.6 77.6 76.3 76.4 Fulchers A -3.407 -3.083 -3.065 -3.373 -3.386 -3.514 -3.437 -3.416 -3.416 -3.247 Fulchers B 8891.5 8247.5 8041.1 8793.4 8767.4 9029.1 8904.5 8684 8789 8225.7 Fulchers To 25.7 63.2 83.9 47.6 46 28.7 34.7 62.8 42.7 97.3 200P temperature (°C) 1583 1595 1582 1597 1588 1581 1587 1582 1580 1580 35000P temperature (°C) 1144 1145 1141 1158 1152 1149 1150 1154 1147 1153 200000P temperature (°C) 1047 1047 1045 1061 1055 1053 1054 1059 1051 1060 Liquid phase viscosity (kiloPoise) 229 229 164 116 201 212 215 132 95 82 SOC (nm / mm / MPa) 2.949 2.963 2.932 2.956 2.924 2.949 2.956 2.932 2.99 2.966 Refractive index 1.5034 1.5027 1.5038 1.5031 1.507 1.5084 1.5074 1.5081 1.5103 1.5091 Young's modulus (GPa) 74.8 74.7 75.1 75.2 77.8 77.4 77.6 78.5 78.2 78.5

[0104] Table 1 - Continuation

[0105] sample 31 32 33 34 35 36 37 38 39 40 <![CDATA[SiO2]]> 61.36 61.41 61.50 61.36 61.27 61.51 70.21 68.19 66.26 72.19 <![CDATA[Al2O3]]> 16.33 16.23 16.14 16.29 16.20 16.27 9.83 11.85 13.81 9.94 <![CDATA[P2O5]]> 2.97 3.47 2.99 2.95 2.97 2.97 0.00 0.00 0.05 0.00 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.98 1.91 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 8.35 8.35 8.37 8.39 8.37 8.34 6.01 6.01 6.01 6.01 <![CDATA[Na2O]]> 10.45 10.46 10.42 10.48 9.90 8.91 13.89 13.89 13.86 11.80 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 0.02 0.02 0.49 0.24 0.01 0.01 0.00 0.00 0.00 0.00 ZnO 0.46 0.02 0.02 0.23 0.23 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.06 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.00 0.05 <![CDATA[Al2O3+Li2O]]> 24.68 24.57 24.51 24.67 24.58 24.62 15.84 17.86 19.82 15.95 <![CDATA[R2O]]> 18.81 18.81 18.80 18.87 18.28 17.26 19.91 19.91 19.88 17.82 <![CDATA[R2O+RO]]> 19.28 18.85 19.31 19.35 18.53 17.28 19.91 19.91 19.88 17.82 <![CDATA[Li2O / Na2O]]> 0.80 0.80 0.80 0.80 0.85 0.94 0.43 0.43 0.43 0.51 <![CDATA[SiO2+Al2O3]]> 77.69 77.63 77.64 77.64 77.47 77.78 80.04 80.04 80.07 82.13 <![CDATA[R2O / Al2O3]]> 1.15 1.16 1.16 1.16 1.13 1.06 2.02 1.68 1.44 1.79 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.66 81.10 80.63 80.60 81.42 82.67 80.04 80.04 80.12 82.13 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 9.66 9.72 9.63 9.61 9.72 9.91 13.32 13.32 13.33 13.67 <![CDATA[Density (g / cm 3 )]]> 2.428 2.414 2.42 2.424 2.409 2.396 2.425 2.433 2.440 2.408 Strain point (°C) 561 568 565 562 552 546 458 475 499 470 Annealing point (°C) 611 618 614 612 604 598 499 517 542 513 Softening point (°C) 850.4 861.2 854.4 853.3 847.5 847.1 705 731 769 735 <![CDATA[10 11 Poise temperature (°C) 694 701 696 695 689 684 568 589 616 587 <![CDATA[CTE*10 -7 (1 / ℃)]]> 82 82.7 82.7 82.2 81.1 76.9 87.1 87.7 88.2 80.3 Fulchers A -3.507 -3.68 -3.151 -3.428 -3.51 -3.293 -1.855 -2.373 -2.668 -1.950 Fulchers B 9164.8 9566 8306 8922.5 9133.7 8482.9 6336.7 7638.0 8386.1 6900.0 Fulchers To 13.3 -0.4 68.6 30.2 15.2 59.6 18.9 -55.9 -76.3 -3.6 200P temperature (°C) 1591 1599 1592 1588 1587 1576 1544 1578 1611 1620 35000P temperature (°C) 1152 1163 1148 1149 1149 1142 1009 1048 1086 1059 200000P temperature (°C) 1054 1065 1051 1052 1052 1047 904 939 976 948 Liquid phase viscosity (kiloPoise) 195 296 308 314 253 127 SOC (nm / mm / MPa) 2.936 2.939 2.933 2.925 2.978 3.047 2.851 2.848 2.862 2.925 Refractive index 1.5074 1.5052 1.5064 1.5071 1.5055 1.5046 1.5054 1.5073 1.5089 1.5028 Young's modulus (GPa) 77.4 76.1 77.2 76.7 76.5 75.3 76.1 77.2 77.6 76.3

[0106] Table 1 - Continuation

[0107] sample 41 42 43 44 45 46 47 48 49 50 <![CDATA[SiO2]]> 70.06 68.13 67.46 66.33 65.30 64.26 63.28 61.85 64.37 63.47 <![CDATA[Al2O3]]> 11.72 13.77 14.72 15.76 16.56 16.85 16.41 16.67 16.86 16.75 <![CDATA[P2O5]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 6.01 6.01 5.71 5.67 5.69 5.83 5.61 5.76 5.81 5.70 <![CDATA[Na2O]]> 12.15 12.03 12.03 12.16 12.37 11.94 12.37 12.38 11.87 11.96 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 0.00 0.00 0.02 0.02 0.02 1.07 2.28 3.29 1.03 2.07 ZnO 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 17.73 19.78 20.43 21.43 22.25 22.68 22.02 22.43 22.67 22.44 <![CDATA[R2O]]> 18.17 18.05 17.75 17.84 18.07 17.77 17.98 18.15 17.69 17.67 <![CDATA[R2O+RO]]> 18.17 18.05 17.77 17.86 18.09 18.85 20.26 21.44 18.72 19.73 <![CDATA[Li2O / Na2O]]> 0.49 0.50 0.47 0.47 0.46 0.49 0.45 0.47 0.49 0.48 <![CDATA[SiO2+Al2O3]]> 81.78 81.90 82.19 82.09 81.86 81.11 79.69 78.51 81.23 80.22 <![CDATA[R2O / Al2O3]]> 1.55 1.31 1.20 1.13 1.09 1.05 1.10 1.09 1.05 1.05 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 81.78 81.90 82.19 82.09 81.86 81.11 79.69 78.51 81.23 80.22 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 13.61 13.63 14.41 14.47 14.39 13.91 14.21 13.63 13.98 14.08 <![CDATA[Density (g / cm 3 )]]> 2.418 2.424 2.425 2.429 2.431 2.438 2.448 2.456 2.438 2.448 Strain point (°C) 486 517 540 565 586 593 575 573 593 575 Annealing point (°C) 530 563 590 616 638 645 625 622 645 625 Softening point (°C) 758 812 843.8 877.9 906.7 905 875.3 860.8 905 875 <![CDATA[10 11 Poise temperature (°C) 606 643 675 703 727 733 710 704 733 710 <![CDATA[CTE*10 -7 (1 / ℃)]]> 81.7 81.9 81.9 82.7 83.7 82.1 82.2 82.4 82.10 82.20 Fulchers A -2.355 -3.091 -4.529 -4.374 -3.951 -3.276 -3.592 -3.062 -3.276 -3.592 Fulchers B 7943.7 9648.4 13672.9 12400.8 10724.5 8698.3 9477.4 8016.7 8698.3 9477.4 Fulchers To -60 -105.5 -318.2 -178.6 -35.9 93.6 10.3 98.2 93.6 10.3 200P temperature (°C) 1646 1684 1684 1679 1679 1653 1619 1593 1653 1619 35000P temperature (°C) 1091 1158 1189 1212 1227 1206 1175 1152 1206 1175 200000P temperature (°C) 978 1044 1073 1103 1123 1108 1076 1057 1108 1076 Liquid phase viscosity (kilopoise) 1472 3182 1853 1519 387 1853 1519 SOC (nm / mm / MPa) 2.909 2.930 2.944 2.944 2.938 2.918 2.873 2.858 2.918 2.873 Refractive index 1.5049 1.5066 1.5068 1.5073 1.5078 1.5100 1.5115 1.5136 1.5100 1.5115 Young's modulus (GPa) 76.9 77.9 78.2 78.0 78.3 79.7 79.9 80.5 79.7 79.9

[0108] Table 1 - Continuation

[0109] sample 51 52 53 54 55 56 57 58 59 60 <![CDATA[SiO2]]> 63.29 63.35 63.24 63.24 63.40 62.05 62.24 62.94 61.72 62.18 <![CDATA[Al2O3]]> 17.46 17.86 17.09 17.47 16.16 16.43 16.30 16.36 16.52 17.02 <![CDATA[P2O5]]> 0.00 0.00 0.00 0.00 0.00 1.10 1.09 0.00 1.10 1.10 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 5.72 5.73 6.00 6.22 6.73 6.20 7.03 6.54 6.92 6.92 <![CDATA[Na2O]]> 11.93 11.93 12.00 11.97 13.64 13.08 13.27 12.93 12.60 12.71 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 1.54 1.07 1.62 1.05 0.02 1.08 0.02 1.18 1.10 0.02 ZnO 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.04 0.05 0.04 0.04 <![CDATA[Al2O3+Li2O]]> 23.18 23.59 23.09 23.69 22.89 22.63 23.33 22.89 23.44 23.94 <![CDATA[R2O]]> 17.66 17.67 18.01 18.19 20.37 19.29 20.31 19.48 19.53 19.63 <![CDATA[R2O+RO]]> 19.20 18.74 19.62 19.24 20.39 20.38 20.33 20.65 20.62 19.66 <![CDATA[Li2O / Na2O]]> 0.48 0.48 0.50 0.52 0.49 0.47 0.53 0.51 0.55 0.54 <![CDATA[SiO2+Al2O3]]> 80.75 81.21 80.33 80.71 79.56 78.48 78.54 79.30 78.24 79.20 <![CDATA[R2O / Al2O3]]> 1.01 0.99 1.05 1.04 1.26 1.17 1.25 1.19 1.18 1.15 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.75 81.21 80.33 80.71 79.56 79.58 79.63 79.30 79.33 80.30 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 14.12 14.17 13.39 12.98 11.83 12.83 11.32 12.13 11.47 11.61 <![CDATA[Density (g / cm 3 )]]> 2.443 2.440 2.444 2.442 2.400 2.400 2.400 2.400 2.400 2.400 Strain point (°C) 601 615 584 592 524 564 545 546 559 573 Annealing point (°C) 654 670 637 644 571 614 593 594 608 624 Softening point (°C) 908 926 889 898 800 857 828 834 846 869 <![CDATA[10 11 Poise temperature (°C) 742 760 724 731 649 697 673 675 690 709 <![CDATA[CTE*10 -7 (1 / ℃)]]> 81.00 80.90 82.20 82.30 88.6 86.6 88.5 87.2 85.9 87.2 Fulchers A -3.607 -3.554 -3.468 -3.723 -3.311 -2.657 -3.409 -3.487 -3.067 -3.525 Fulchers B 9163.8 8892.3 8990.5 9397 9487.1 7241.1 9457.1 9503.6 8245.3 9417.5 Fulchers To 76.5 118.3 64.2 59.4 -89.7 149.4 -55.3 -43.1 61.3 3.3 200P temperature (°C) 1628 1637 1623 1619 1601 1610 1601 1599 1597 1620 35000P temperature (°C) 1201 1216 1186 1196 1118 1155 1134 1140 1145 1170 200000P temperature (°C) 1105 1123 1089 1101 1012 1059 1030 1038 1047 1070 Liquid phase viscosity (kiloPoise) 1275 1401 1378 1147 207 1299 805 283 906 839 SOC (nm / mm / MPa) 2.918 2.895 2.908 2.814 2.888 2.864 2.852 2.864 2.888 Refractive index 1.5111 1.5115 1.5114 1.5121 1.5088 1.5097 1.5122 1.5102 1.5093 Young's modulus (GPa) 80.0 80.0 80.2 79.4 78.0 77.9 79.6 78.8 78.3

[0110] Table 1 - Continuation

[0111] sample 61 62 63 64 65 66 67 68 69 70 <![CDATA[SiO2]]> 62.34 62.24 62.32 62.25 62.24 62.26 61.38 60.52 59.63 58.66 <![CDATA[Al2O3]]> 17.25 17.22 17.22 17.23 17.24 17.25 16.32 16.41 16.48 16.48 <![CDATA[P2O5]]> 1.09 1.06 1.04 1.05 1.06 1.05 0.93 1.93 2.91 3.93 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 7.14 7.56 7.70 7.30 7.57 7.80 7.00 7.08 7.17 7.13 <![CDATA[Na2O]]> 12.11 11.84 11.64 11.70 11.42 11.18 12.71 12.47 12.27 12.26 <![CDATA[K2O]]> 0.01 0.01 0.01 0.40 0.40 0.40 0.52 0.50 0.49 0.49 MgO 0.02 0.02 0.02 0.02 0.03 0.02 1.09 1.04 1.01 1.00 ZnO 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.04 0.04 0.05 0.04 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 24.39 24.78 24.93 24.54 24.82 25.05 23.32 23.48 23.65 23.61 <![CDATA[R2O]]> 19.26 19.41 19.35 19.40 19.39 19.38 20.23 20.05 19.93 19.88 <![CDATA[R2O+RO]]> 19.28 19.44 19.37 19.42 19.41 19.40 21.33 21.09 20.94 20.89 <![CDATA[Li2O / Na2O]]> 0.59 0.64 0.66 0.62 0.66 0.70 0.55 0.57 0.58 0.58 <![CDATA[SiO2+Al2O3]]> 79.59 79.46 79.54 79.48 79.48 79.51 77.70 76.93 76.11 75.14 <![CDATA[R2O / Al2O3]]> 1.12 1.13 1.12 1.10 1.10 1.10 1.21 1.19 1.18 1.18 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.68 80.51 80.59 80.53 80.54 80.55 78.63 78.86 79.02 79.07 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 11.29 10.65 10.46 11.03 10.64 10.33 11.23 11.15 11.02 11.09 <![CDATA[Density (g / cm 3 )]]> 2.434 2.433 2.432 2.434 2.433 2.433 2.449 2.440 2.436 2.433 Strain point (°C) 585 584 590 584 584 582 538 555 566 565 Annealing point (°C) 636 636 641 635 635 634 586 601 609 607 Softening point (°C) 883.1 878.9 878.6 879.5 879.9 879.3 817.4 836.8 846.9 844.2 <![CDATA[10 11 Poise temperature (°C) 721 721 724 720 720 720 666 680 685 682 <![CDATA[CTE*10 -7 (1 / ℃)]]> 85.6 85.9 84.8 86.6 85.4 86.1 90.10 90.10 90.20 90.60 Fulchers A -3.325 -3.869 -3.268 -3.432 -3.955 -3.373 -3.493 -3.199 -3.556 Fulchers B 8741 10051.8 8568.8 9057.8 10392.1 8843.4 9216.9 8403.2 9085.3 Fulchers To 67.1 -17.3 75.5 45.5 -42.4 57.3 -17.4 49.2 10.1 200P temperature (°C) 1621 1612 1614 1625 1619 1616 1573 1577 1561 35000P temperature (°C) 1178 1177 1172 1181 1180 1174 1129 1134 1132 200000P temperature (°C) 1080 1079 1075 1083 1080 1077 1031 1038 1036 Liquid phase viscosity (kiloPoise) 788 482 512 587 604 381 1530 1519 1638 SOC (nm / mm / MPa) 2.930 2.923 2.922 2.906 2.903 2.897 2.823 2.877 2.880 2.880 Refractive index 1.5093 1.5096 1.5098 1.5093 1.5096 1.5100 1.5113 1.5085 1.5069 1.5052 Young's modulus (GPa) 78.5 78.9 78.7 78.4 78.9 78.9 79.4 78.0 77.0 75.6

[0112] Table 1 - Continuation

[0113] sample 71 72 73 74 75 76 77 78 79 80 <![CDATA[SiO2]]> 57.73 56.66 64.38 63.28 62.39 61.36 60.45 59.40 64.30 63.25 <![CDATA[Al2O3]]> 16.49 16.46 16.17 16.28 16.25 16.31 16.30 16.27 16.15 16.26 <![CDATA[P2O5]]> 4.92 5.91 0.00 0.94 1.90 2.94 3.93 5.02 0.00 0.97 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 7.11 7.20 8.65 8.74 8.77 8.81 8.83 8.81 9.25 9.29 <![CDATA[Na2O]]> 12.21 12.21 10.72 10.68 10.61 10.48 10.45 10.47 10.22 10.14 <![CDATA[K2O]]> 0.49 0.49 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 1.00 1.01 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 ZnO 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.00 0.01 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 23.60 23.66 24.82 25.01 25.02 25.13 25.13 25.07 25.40 25.55 <![CDATA[R2O]]> 19.81 19.91 19.38 19.43 19.39 19.31 19.29 19.29 19.48 19.44 <![CDATA[R2O+RO]]> 20.81 20.92 19.40 19.45 19.41 19.33 19.31 19.31 19.50 19.46 <![CDATA[Li2O / Na2O]]> 0.58 0.59 0.81 0.82 0.83 0.84 0.85 0.84 0.90 0.92 <![CDATA[SiO2+Al2O3]]> 74.22 73.12 80.55 79.56 78.64 77.68 76.75 75.67 80.45 79.52 <![CDATA[R2O / Al2O3]]> 1.17 1.18 1.20 1.19 1.19 1.18 1.18 1.19 1.21 1.19 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 79.14 79.03 80.55 8050 80.54 80.62 80.68 80.69 80.45 80.49 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 11.13 10.97 9.31 9.22 9.18 9.15 9.13 9.16 8.70 8.66 <![CDATA[Density (g / cm 3 )]]> 2.428 2.425 2.434 2.429 2.424 2.419 2.415 2.411 2.433 2.426 Strain point (°C) 563 545 535 553 563 562 560 551 535 552 Annealing point (°C) 608 591 582 600 612 611 609 601 581 600 Softening point (°C) 837.6 827.1 818.1 837.4 849.8 849.2 849.8 840.8 810 <![CDATA[10 11 Poise temperature (°C) 685 670 661 679 693 692 690 683 658 <![CDATA[CTE*10 -7 (1 / ℃)]]> 90.00 90.30 83.6 83.8 83.6 84.6 84.1 84.2 82.7 82.5 Fulchers A -3.161 -3.588 -3.826 -3.63 -2.79 -3.512 -3.12 -3.28 -2.877 -3.537 Fulchers B 8180.3 9097.4 10478.8 9677.6 7575.6 9191.9 8193.7 8569.4 8126.3 9491.6 Fulchers To 66.5 3.9 -115.5 -39.6 110.2 5.7 74.7 43.8 31 -34.9 200P temperature (°C) 1564 1549 1595 1592 1598 1587 1586 1579 1600 1591 35000P temperature (°C) 1128 1123 1136 1144 1143 1147 1144 1139 1126 1140 200000P temperature (°C) 1033 1027 1033 1044 1046 1049 1048 1042 1025 1039 Liquid phase viscosity (kiloPoise) 2331 5458 123 148 127 215 233 388 81 124 SOC (nm / mm / MPa) 2.889 2.882 2.878 2.900 2.915 2.914 2.926 2.882 Refractive index 1.5040 1.5023 1.5111 1.5089 1.5070 1.5055 1.5036 1.5112 Young's modulus (GPa) 74.7 73.1 79.7 78.5 77.2 75.8 74.7 79.8

[0114] Table 1 - Continuation

[0115] sample 81 82 83 84 85 86 87 88 89 90 <![CDATA[SiO2]]> 62.53 61.40 60.37 59.50 64.10 63.35 62.25 61.33 60.37 59.47 <![CDATA[Al2O3]]> 16.28 16.30 16.27 16.22 16.31 16.22 16.33 16.30 16.28 16.22 <![CDATA[P2O5]]> 1.94 2.91 3.93 4.87 0.00 0.94 1.95 2.88 3.89 4.85 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 9.11 9.27 9.31 9.34 9.83 9.76 9.86 9.91 9.86 9.90 <![CDATA[Na2O]]> 10.06 10.03 10.03 9.99 9.68 9.64 9.55 9.49 9.52 9.48 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 0.02 ZnO 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 25.39 25.57 25.58 25.56 26.14 25.99 26.18 26.21 26.14 26.11 <![CDATA[R2O]]> 19.17 19.31 19.34 19.34 19.52 19.41 19.41 19.41 19.39 19.38 <![CDATA[R2O+RO]]> 19.20 19.33 19.37 19.36 19.54 19.43 19.44 19.43 19.41 19.41 <![CDATA[Li2O / Na2O]]> 0.91 0.92 0.93 0.94 1.02 1.01 1.03 1.04 1.04 1.04 <![CDATA[SiO2+Al2O3]]> 78.81 77.70 76.65 75.73 80.41 79.58 78.57 77.64 76.65 75.69 <![CDATA[R2O / Al2O3]]> 1.18 1.18 1.19 1.19 1.20 1.20 1.19 1.19 1.19 1.19 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.75 80.62 80.58 80.59 80.41 80.52 80.52 80.52 80.54 80.54 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 8.87 8.69 8.66 8.63 8.18 8.25 8.17 8.13 8.17 8.14 <![CDATA[Density (g / cm 3 )]]> 2.422 2.418 2.414 2.410 2.431 2.425 2.420 2.416 2.412 2.408 Strain point (°C) 560 563 556 547 537 550 559 561 556 547 Annealing point (°C) 609 612 606 596 584 599 608 610 605 597 Softening point (°C) 844.9 849.7 845.3 836.2 841.4 845 841.7 835.3 <![CDATA[10 11 Poise temperature (°C) 690 693 688 677 689 691 686 679 <![CDATA[CTE*10 -7 (1 / ℃)]]> 82.8 83.6 83.5 84 81.7 81.9 82.6 82.5 83.3 83.2 Fulchers A -3.174 -3.318 -2.859 -3.164 -2.948 -3.471 -3.167 -2.681 -3.336 -3.133 Fulchers B 8419.1 8713 7568.2 8218.3 8181 9289.7 8361.2 7083.5 8632.9 8110.1 Fulchers To 56.7 38.3 114.3 68.4 32.2 -23.8 54.2 163.2 36.4 71.8 200P temperature (°C) 1594 1589 1581 1572 1591 1586 1583 1585 1568 1564 35000P temperature (°C) 1148 1147 1137 1135 1124 1135 1139 1144 1132 1128 200000P temperature (°C) 1050 1049 1042 1039 1024 1035 1042 1051 1036 1033 Liquid phase viscosity (kilopoise) 113 122 170 218 48 68 62 92 86 74 SOC (nm / mm / MPa) 2.882 2.907 2.915 2.917 2.879 2.895 2.899 2.904 2.924 Refractive index 1.5090 1.5072 1.5057 1.5042 1.5119 1.5100 1.5082 1.5064 1.5048 Young's modulus (GPa) 78.3 77.4 76.2 75.1 80.1 78.8 77.6 76.5 75.3

[0116] Table 1 - Continuation

[0117] sample 91 92 93 94 95 96 97 98 99 100 <![CDATA[SiO2]]> 60.33 60.44 60.38 60.32 60.45 60.35 61.46 61.49 61.41 61.38 <![CDATA[Al2O3]]> 16.31 16.26 16.28 16.26 16.27 16.23 16.26 16.26 16.23 16.25 <![CDATA[P2O5]]> 3.92 3.88 3.95 4.00 3.91 4.02 2.92 2.90 2.95 2.97 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Li2O]]> 8.38 8.43 8.37 8.33 8.45 8.39 7.80 7.85 7.87 7.85 <![CDATA[Na2O]]> 10.00 9.98 9.97 9.04 8.97 9.00 10.49 10.50 10.51 9.48 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 1.01 0.02 0.50 1.99 0.02 1.01 1.02 0.02 0.51 2.01 ZnO 0.00 0.94 0.49 0.00 1.87 0.95 0.00 0.93 0.47 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 24.69 24.68 24.65 24.59 24.72 24.62 24.06 24.11 24.10 24.10 <![CDATA[R2O]]> 18.38 18.42 18.35 17.38 17.43 17.40 18.30 18.35 18.39 17.34 <![CDATA[R2O+RO]]> 19.39 19.37 19.34 19.37 19.32 19.36 19.32 19.31 19.37 19.36 <![CDATA[Li2O / Na2O]]> 0.84 0.84 0.84 0.92 0.94 0.93 0.74 0.75 0.75 0.83 <![CDATA[SiO2+Al2O3]]> 76.64 76.70 76.66 76.58 76.73 76.57 77.71 77.74 77.64 77.62 <![CDATA[R2O / Al2O3]]> 1.13 1.13 1.13 1.07 1.07 1.07 1.13 1.13 1.13 1.07 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.56 80.58 80.61 80.58 80.63 80.59 80.63 80.65 80.59 80.59 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 9.62 9.56 9.63 9.67 9.54 9.60 10.33 10.28 10.24 10.26 <![CDATA[Density (g / cm 3 )]]> 2.418 2.430 2.423 2.418 2.444 2.430 2.422 2.436 2.428 2.423 Strain point (°C) 563 555 558 568 555 560 570 564 566 575 Annealing point (°C) 611 606 607.0 616 605 610 620 615 616 624 Softening point (°C) 854.9 850.1 850.4 857.2 851.8 852.1 860.4 858.1 859.7 865.6 <![CDATA[10 11 Poise temperature (°C) 695 688 689 698 688 691 701 697 699 706 <![CDATA[CTE*10 -7 (1 / ℃)]]> 82.3 80.6 80.5 77.3 76.2 76.4 80.8 81.2 81 78.1 Fulchers A -3.335 -3.361 -3.421 -3.467 -3.405 -3.44 -3.108 -3.484 -3.386 -2.992 Fulchers B 8633.5 8739.7 8866.5 8755.7 8753.7 8798.6 8110.4 9086.5 8788.5 7780.3 Fulchers To 55 39 35.9 54.3 42.8 42.9 99.8 27.8 50.7 115.7 200P temperature (°C) 1587 1583 1585 1572 1577 1575 1599 1598 1596 1586 35000P temperature (°C) 1151 1145 1149 1147 1144 1145 1160 1160 1159 1148 200000P temperature (°C) 1055 1048 1052 1053 1048 1049 1064 1062 1062 1054 Liquid phase viscosity (kiloPoise) 243 192 257 142 108 134 367 281 314 216 SOC (nm / mm / MPa) 2.932 2.966 2.932 2.934 2.988 2.961 2.92 2.962 2.925 2.929 Refractive index 1.5055 1.5067 1.5059 1.5060 1.5086 1.5069 1.5062 1.5075 1.5070 1.5074 Young's modulus (GPa) 76.2 76.1 76.3 77.2 77.1 77.2 77.0 77.3 77.2 78.2

[0118] Table 1 - Continuation

[0119] sample 101 102 103 104 105 106 107 108 <![CDATA[SiO2]]> 61.27 61.34 61.36 61.41 61.50 61.36 61.27 61.51 <![CDATA[Al2O3]]> 16.24 16.34 16.33 16.23 16.14 16.29 16.20 16.27 <![CDATA[P2O5]]> 2.98 2.96 2.97 3.47 2.99 2.95 2.97 2.97 <![CDATA[B2O3]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.98 1.91 <![CDATA[Li2O]]> 7.98 7.85 8.35 8.35 8.37 8.39 8.37 8.34 <![CDATA[Na2O]]> 9.50 9.53 10.45 10.46 10.42 10.48 9.90 8.91 <![CDATA[K2O]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 MgO 0.03 1.00 0.02 0.02 0.49 0.24 0.01 0.01 ZnO 1.94 0.93 0.46 0.02 0.02 0.23 0.23 0.00 <![CDATA[SnO2]]> 0.05 0.05 0.06 0.05 0.05 0.05 0.05 0.05 <![CDATA[Al2O3+Li2O]]> 24.22 24.19 24.68 24.57 24.51 24.67 24.58 24.62 <![CDATA[R2O]]> 17.49 17.39 18.81 18.81 18.80 18.87 18.28 17.26 <![CDATA[R2O+RO]]> 19.45 19.31 19.28 18.85 19.31 19.35 18.53 17.28 <![CDATA[Li2O / Na2O]]> 0.84 0.82 0.80 0.80 0.80 0.80 0.85 0.94 <![CDATA[SiO2+Al2O3]]> 77.51 77.67 77.69 77.63 77.64 77.64 77.47 77.78 <![CDATA[R2O / Al2O3]]> 1.08 1.06 1.15 1.16 1.16 1.16 1.13 1.06 <![CDATA[SiO2+Al2O3+B2O3+P2O5]]> 80.49 80.64 80.66 81.10 80.63 80.60 81.42 82.67 <![CDATA[(SiO2+Al2O3+B2O3+P2O5) / Li2O]]> 10.09 10.27 9.66 9.72 9.63 9.61 9.72 9.91 <![CDATA[Density (g / cm 3 )]]> 2.449 2.437 2.428 2.414 2.42 2.424 2.409 2.396 Strain point (°C) 563 565 561 568 565 562 552 546 Annealing point (°C) 614 615 611 618 614 612 604 598 Softening point (°C) 859.2 860.8 850.4 861.2 854.4 853.3 847.5 847.1 <![CDATA[10 11 Poise temperature (°C) 698 699 694 701 696 695 689 684 <![CDATA[CTE*10 -7 (1 / ℃)]]> 77 76.7 82 82.7 82.7 82.2 81.1 76.9 Fulchers A -3.613 -3.506 -3.507 -3.68 -3.151 -3.428 -3.51 -3.293 Fulchers B 9324.8 8964.3 9164.8 9566 8306 8922.5 9133.7 8482.9 Fulchers To 1.6 39.9 13.3 -0.4 68.6 30.2 15.2 59.6 200P temperature (°C) 1578 1584 1591 1599 1592 1588 1587 1576 35000P temperature (°C) 1145 1153 1152 1163 1148 1149 1149 1142 200000P temperature (°C) 1048 1058 1054 1065 1051 1052 1052 1047 Liquid phase viscosity (kilopoise) 143 157 195 296 308 314 253 127 SOC (nm / mm / MPa) 2.987 2.963 2.936 2.939 2.933 2.925 2.978 3.047 Refractive index 1.5096 1.5090 1.5074 1.5052 1.5064 1.5071 1.5055 1.5046 Young's modulus (GPa) 77.9 78.1 77.4 76.1 77.2 76.7 76.5 75.3

[0120] Unless otherwise stated, all compositional details, relationships, and proportions described in this specification are provided in mol%. All scopes disclosed in this specification include any and all scopes and subscopes covered by the broadly disclosed scope, whether or not explicitly stated before or after the disclosure.

[0121] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and variations to the various embodiments described herein, provided that such modifications and variations fall within the scope of the appended claims and their equivalents.

[0122] As used in this article, trailing zeros in a number are intended to indicate the number of significant digits. For example, the number "1.0" has two significant digits, while the number "1.00" has three significant digits.

Claims

1. A glass composition comprising: SiO2 with a content greater than or equal to 55.0 mol% and less than or equal to 75.0 mol%; Al2O3 with a content greater than or equal to 8.0 mol% to less than or equal to 20.0 mol%; Li₂O with a concentration greater than or equal to 3.0 mol% to less than or equal to 15.0 mol%; Greater than or equal to 5.0 mol% to less than or equal to 15.0 mol% of Na2O; B2O3 greater than or equal to 1.0 mol%; Less than or equal to 7.5 mol% of B₂O₃ + P₂O₅; and K₂O content less than or equal to 1.5 mol%, in: Al₂O₃ + Li₂O > 22.5 mol%. R₂O + RO is greater than or equal to 18.0 mol%. Al₂O₃ + Li₂O + Na₂O ≥ 34 mol%. The concentrations of SiO2 + Al2O3 + B2O3 + P2O5 are greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.

0.

2. The glass composition of claim 1, wherein Al₂O₃ + Li₂O is greater than or equal to 23.0 mol%.

3. The glass composition of claim 1 or 2, wherein Al2O3 + Li2O is greater than or equal to 23.0 mol% to less than or equal to 26.5 mol%.

4. The glass composition of claim 1 or 2, wherein R₂O + RO is greater than or equal to 18.0 mol% to less than or equal to 23.0 mol%.

5. The glass composition of claim 1 or 2, wherein R₂O + RO is greater than or equal to 19.0 mol% to less than or equal to 22.0 mol%.

6. The glass composition of claim 1 or 2, wherein the R2O / Al2O3 ratio is greater than or equal to 1.10 to less than or equal to 2.

10.

7. The glass composition of claim 1 or 2, wherein the R2O / Al2O3 ratio is greater than or equal to 1.10 and less than or equal to 1.

90.

8. The glass composition of claim 1 or 2, wherein SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol% to less than or equal to 85.0 mol%.

9. The glass composition of claim 1 or 2, wherein SiO2+Al2O3+B2O3+P2O5 is greater than or equal to 78.0 mol% to less than or equal to 83.0 mol%.

10. The glass composition of claim 1 or 2, wherein (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.0 and less than or equal to 17.

0.

11. The glass composition of claim 1 or 2, wherein (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 10.0 and less than or equal to 15.

0.

12. The glass composition of claim 1 or 2, wherein the glass composition comprises greater than or equal to 2.0 mol% B2O3.

13. The glass composition of claim 1 or 2, wherein the softening point of the glass composition is less than or equal to 855°C.

14. The glass composition of claim 1 or 2, wherein the softening point of the glass composition is greater than or equal to 700°C and less than or equal to 855°C.

15. A glass article comprising: First surface; A second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed as the distance between the first surface and the second surface; and A compressive stress layer extends from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein The center tension of the glass product is greater than or equal to 30 MPa. The compression depth of the compressive stress layer is greater than or equal to 0.15t and less than or equal to 0.25t, and The glass product is formed of glass, and the glass comprises: SiO2 with a content greater than or equal to 55.0 mol% and less than or equal to 75.0 mol%; Al2O3 with a content greater than or equal to 8.0 mol% to less than or equal to 20.0 mol%; Li₂O with a concentration greater than or equal to 3.0 mol% to less than or equal to 15.0 mol%; Greater than or equal to 5.0 mol% to less than or equal to 15.0 mol% of Na2O; B2O3 greater than or equal to 1.0 mol%; Less than or equal to 7.5 mol% of B₂O₃ + P₂O₅; and K₂O content less than or equal to 1.5 mol%, in: Al₂O₃ + Li₂O > 22.5 mol%. R₂O + RO is greater than or equal to 18.0 mol%. Al₂O₃ + Li₂O + Na₂O ≥ 34 mol%. The concentrations of SiO2 + Al2O3 + B2O3 + P2O5 are greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.

0.

16. The glass article of claim 15, wherein the center tension of the glass article is greater than or equal to 50 MPa.

17. The glass article as claimed in claim 15 or 16, wherein the center tension of the glass article is greater than or equal to 80 MPa.

18. The glass article of claim 15 or 16, wherein the potassium in the compressive stress layer penetrates to a depth greater than 5 μm and less than or equal to 45 μm into the thickness of the glass article.

19. The glass article of claim 15 or 16, wherein the liquid phase viscosity of the glass is greater than or equal to 20 kP and less than 1000 kP.

20. The glass article of claim 15 or 16, wherein the surface compressive stress of the compressive stress layer is greater than or equal to 450 MPa and less than or equal to 800 MPa.

21. The glass article of claim 15 or 16, wherein the glass comprises 2.0 mol% or more of B2O3.

22. The glass article of claim 15 or 16, wherein the softening point of the glass is less than or equal to 855°C.

23. The glass article of claim 15 or 16, wherein the softening point of the glass is greater than or equal to 700°C and less than or equal to 855°C.

24. A consumer electronics product, comprising: A housing, the housing including a front surface, a rear surface and side surfaces; Electrical components located at least partially within the housing, including at least a controller, a memory, and a display, the display being located at or near the front surface of the housing; and Cover substrate disposed above the display At least a portion of at least one of the housing and the cover substrate comprises the glass article as described in claim 15 or 16.

25. A glass article comprising: First surface; A second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed as the distance between the first surface and the second surface; and A compressive stress layer extends from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein The center tension of the glass product is greater than or equal to 60 MPa. The compression depth of the compressive stress layer is greater than or equal to 0.15t and less than or equal to 0.25t, and The glass article has a composition at a central depth of the glass article, the composition comprising: SiO2 with a content greater than or equal to 55.0 mol% and less than or equal to 75.0 mol%; Al2O3 with a content greater than or equal to 8.0 mol% to less than or equal to 20.0 mol%; Li₂O with a concentration greater than or equal to 3.0 mol% to less than or equal to 15.0 mol%; Greater than or equal to 5.0 mol% to less than or equal to 15.0 mol% Na2O; B2O3 greater than or equal to 1.0 mol%; Less than or equal to 7.5 mol% of B₂O₃ + P₂O₅; and K₂O content less than or equal to 1.5 mol%, in: Al₂O₃ + Li₂O > 22.5 mol%. R₂O + RO is greater than or equal to 18.0 mol%. Al₂O₃ + Li₂O + Na₂O ≥ 34 mol%. The concentrations of SiO2 + Al2O3 + B2O3 + P2O5 are greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 8.

0.

26. The glass article of claim 25, wherein the composition comprises 2.0 mol% or more of B2O3.

27. The glass article of claim 25, wherein the softening point of the composition is less than or equal to 855°C.

28. The glass article of claim 25, wherein the softening point of the composition is greater than or equal to 700°C and less than or equal to 855°C.

29. A glass composition comprising: 55.0 mol% to 70.0 mol% of SiO2; Al2O3 with a content greater than or equal to 10.0 mol% to less than or equal to 20.0 mol%; Li₂O with a concentration greater than or equal to 3.0 mol% to less than or equal to 15.0 mol%; Greater than or equal to 5.0 mol% to less than or equal to 15.0 mol% Na2O; B2O3 greater than or equal to 1.0 mol%; Less than or equal to 7.5 mol% of B₂O₃ + P₂O₅; and K₂O content less than or equal to 1.5 mol%, in: Al₂O₃ + Li₂O > 22.5 mol%. R₂O + RO is greater than or equal to 18.0 mol%. The concentrations of SiO2 + Al2O3 + B2O3 + P2O5 are greater than or equal to 78.0 mol%, and (SiO2+Al2O3+B2O3+P2O5) / Li2O is greater than or equal to 10.

50.

30. The glass composition of claim 29, wherein the glass composition comprises 2.0 mol% or more of B2O3.

31. The glass composition of claim 29, wherein the softening point of the glass composition is less than or equal to 855°C.

32. The glass composition of claim 29, wherein the softening point of the glass composition is greater than or equal to 700°C and less than or equal to 855°C.

33. A glass article comprising: First surface; A second surface opposite to the first surface, wherein the thickness (t) of the glass article is expressed as the distance between the first surface and the second surface; and A compressive stress layer extends from at least one of the first surface and the second surface to the thickness (t) of the glass article, wherein The center tension of the glass product is greater than or equal to 30 MPa. The compression depth of the compressive stress layer is greater than or equal to 0.15t and less than or equal to 0.25t, and The glass article is formed from the glass according to claim 29.

34. The glass article of claim 33, wherein the center tension of the glass article is greater than or equal to 50 MPa.

35. The glass article as claimed in claim 33 or 34, wherein the center tension of the glass article is greater than or equal to 80 MPa.

36. The glass article of claim 33 or 34, wherein the potassium in the compressive stress layer penetrates to a depth greater than 5 μm and less than or equal to 45 μm into the thickness of the glass article.

37. The glass article of claim 33 or 34, wherein the liquid phase viscosity of the glass is greater than or equal to 20 kP and less than 1000 kP.

38. The glass article as claimed in claim 33 or 34, wherein the surface compressive stress of the compressive stress layer is greater than or equal to 450 MPa and less than or equal to 800 MPa.

39. A consumer electronics product, comprising: A housing, the housing including a front surface, a rear surface and side surfaces; Electrical components located at least partially within the housing, including at least a controller, a memory, and a display, the display being located at or near the front surface of the housing; and Cover substrate disposed above the display At least a portion of at least one of the housing and the cover substrate comprises the glass article as described in claim 33 or 34.

Citation Information

Patent Citations

  • Glasses and glass ceramics including a metal oxide concentration gradient

    US20160102011A1

  • Systems and methods for measuring a profile characteristic of a glass sample

    US8854623B2